Metal composite hydroxide and method for producing same, positive electrode active material for nonaqueous electrolyte secondary battery and method for producing same, and nonaqueous electrolyte secondary battery
By using lithium metal composite oxides with core-shell structure, the problem of difficult to take into account both thermal stability and weather resistance while improving the charge and discharge capacity and energy density of lithium-ion secondary batteries is solved, and efficient battery performance is achieved.
Patent Information
- Application Number
- CN202510123941.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2018-02-22
- Filing Date
- 2019-02-20
- Publication Date
- 2025-04-25
AI Technical Summary
While the existing lithium-ion secondary batteries increase the charge and discharge capacity and energy density, thermal stability and weather resistance are difficult to take into account, especially when the particle size distribution width increases, thermal stability decreases and weather resistance to moisture and gas is insufficient.
The lithium metal composite oxide with a core-shell structure is used as the positive electrode active material, and its particle size distribution is controlled within a specific range. By adjusting the composition of the inner and surface of the particles, thermal stability and weather resistance are improved.
It achieves the balance of high charge and discharge capacity, thermal stability and weather resistance in secondary batteries, improves the overall performance of the battery, and is suitable for battery applications with high energy density and long life.
Smart Images

Figure CN119890295A_ABST
Abstract
Description
[0001] This application is a divisional application of the original application, with the application date of February 20, 2019, the application number 201980014631.X, and the invention name of "Metal composite hydroxide and its production method, positive electrode active material for non-aqueous electrolyte secondary battery and its production method, and non-aqueous electrolyte secondary battery". Technical Field
[0002] The present invention relates to a metal composite hydroxide and a method for producing the same, a positive electrode active material for a non-aqueous electrolyte secondary battery and a method for producing the same, and a non-aqueous electrolyte secondary battery. Background Art
[0003] In recent years, with the popularization of portable electronic devices such as mobile phones and notebook computers, there is a strong desire to develop small and lightweight secondary batteries with high energy density. In addition, there is a strong desire to develop secondary batteries with excellent energy density as batteries for xEVs mainly used in electric vehicles.
[0004] As a secondary battery that meets such requirements, there is a lithium ion secondary battery, which is one of the non-aqueous electrolyte secondary batteries. A lithium ion secondary battery is composed of a negative electrode, a positive electrode, and an electrolyte, and the active materials used in the negative electrode material and the positive electrode material use materials that can release and insert lithium.
[0005] Lithium ion secondary batteries are currently being actively researched and developed. Among them, lithium ion secondary batteries using layered or spinel lithium metal composite oxides as positive electrode materials are being put into practical use as batteries with high energy density because they can obtain a high voltage of 4V.
[0006] As the main positive electrode materials proposed so far, there are lithium cobalt composite oxide (LiCoO2) which is relatively easy to synthesize, lithium nickel composite oxide (LiNiO2) which uses nickel which is cheaper than cobalt, and lithium nickel cobalt manganese composite oxide (LiNiO2). 1 / 3Co 1 / 3 Mn 1 / 3 O2), lithium manganese composite oxide (LiMn2O4) using manganese, etc.
[0007] In order to obtain a lithium-ion secondary battery with excellent energy density, it is necessary to make the positive electrode active material have a high charge and discharge capacity. Lithium nickel composite oxide has a lower electrochemical potential than lithium cobalt composite oxide, and the change in the valence of the transition metal contributing to charge and discharge increases, thereby enabling the high capacity of the secondary battery, but on the other hand, compared with lithium cobalt composite oxide and lithium nickel cobalt manganese composite oxide, the thermal stability decreases. Therefore, a number of technologies for improving battery characteristics by making the surface and interior of the particles constituting the lithium metal composite oxide or its precursor have different compositions have been proposed.
[0008] For example, Patent Document 1 proposes a nickel-manganese composite hydroxide particle, which is a precursor of a positive electrode active material for a non-aqueous electrolyte secondary battery and is composed of the general formula: Ni x Mn y Co z M t (OH) 2+α A nickel-manganese composite hydroxide represented by (x+y+z+t=1, 0.3≤x≤0.7, 0.1≤y≤0.55, 0≤z≤0.4, 0≤t≤0.1, -0.5≤α≤0.5, M is one or more additional elements selected from Al, Ti, V, Cr, Zr, Nb, Hf, Ta, Mo, W), wherein [(D90-D10) / MV] as an index representing the width of particle size distribution is 0.55 or less, and a multilayer structure is formed in which the composition inside and outside the secondary particle is different, and the Mn / Ni ratio of the composition outside the secondary particle is higher than that inside the secondary particle. According to Patent Document 1, the above-mentioned nickel-manganese composite hydroxide particles have high uniformity of particle size, can reduce the alkalinity as an active material, and can achieve high capacity and high output when used in secondary batteries.
[0009] In addition, Patent Document 2 proposes a composition having: a) an empirical formula: Li x M′ z Ni 1-y M″ y O2 core and b) a coating having a greater cobalt / nickel ratio than the above core, wherein x is approximately greater than 0.1 and less than approximately 1.3, y is approximately greater than 0.0 and less than approximately 0.5, z is approximately greater than 0.0 and less than approximately 0.2, M′ is at least one element selected from the group consisting of sodium, potassium, calcium, magnesium and strontium, and M″ is at least one element selected from the group consisting of cobalt, iron, manganese, chromium, vanadium, titanium, magnesium, silicon, boron, aluminum and gallium). According to Patent Document 2, the above composition shows improved capacity, cycle characteristics and safety compared to corresponding LiCoO2 and LiNiO2.
[0010] In addition, Patent Document 3 proposes a composite oxide represented by the following formula (1): Li x MeO 2+0.5(x-1)···(1) (wherein Me is a transition metal comprising Ni and at least one metal selected from other transition metals, and x represents a number greater than 1.00 and less than 1.25.) A particulate composite oxide represented by the atomic ratio of Ni to Me (A=Ni / Me×100) is 60 mol% to 90 mol% in the entire particle, and the value of the atomic ratio is smaller in the peripheral portion than in the central portion. According to Patent Document 3, the composite oxide has excellent capacity characteristics and is used as a thermally stable and highly safe positive electrode active material.
[0011] Prior art literature
[0012] Patent Literature
[0013] Patent Document 1: Japanese Patent Application Publication No. 2012-256435
[0014] Patent Document 2: International Publication No. 2002 / 103824
[0015] Patent Document 3: Japanese Patent Application Publication No. 2014-040363 Summary of the invention
[0016] Problems to be solved by the invention
[0017] The lithium metal composite oxides or their precursors described in Patent Documents 1 to 3 have different compositions on the surface and inside of the particles, thereby improving the battery characteristics. However, in secondary batteries, further improvements in charge and discharge capacity and energy density are required along with improved thermal stability.
[0018] As one of the methods for improving the energy density of secondary batteries, a method for increasing the particle size distribution width of the positive electrode active material can be cited. By increasing the particle size distribution of the positive electrode active material, the filling property when forming the pole plate is excellent, so that the amount of active material per unit volume, that is, the charge and discharge capacity, can be increased. However, in the case of increasing the particle size distribution width, particles with a small particle size will increase relatively. Such small-sized particles have a high surface ratio relative to the entire block, so there will be problems such as decreased thermal stability. So far, the characteristics of the material with improved surface composition in the lithium metal composite oxide with a wide particle size distribution and the suitable conditions of the manufacturing method have not been reported.
[0019] Furthermore, as the demand for secondary batteries increases, positive electrode active materials having properties (weather resistance) that are not easily deteriorated by moisture and gas in the atmosphere during the manufacturing process and storage of secondary batteries are required. However, in the above-mentioned Patent Documents 1 to 3, no research is conducted on weather resistance.
[0020] In view of the above problems, the object of the present invention is to provide a positive electrode active material and its precursor that take into account the high charge and discharge capacity, thermal stability and weather resistance of a secondary battery at a higher level. In addition, the object is to provide a manufacturing method, which is a manufacturing method of the positive electrode active material and the precursor, and can easily achieve industrial-scale manufacturing. In addition, the object of the present invention is to provide a secondary battery using such a positive electrode active material.
[0021] Methods for solving problems
[0022] In order to solve the above-mentioned problems, the inventors have carefully studied and found that: a lithium metal composite oxide having a specific core-shell structure with different Ni ratios on the particle surface and inside the particle and controlling the particle size distribution within a specific range is used as a secondary battery of a positive electrode active material and has a high charge and discharge capacity, and is also excellent in weather resistance and thermal stability. It is further found that by controlling the composition inside the particle and controlling the particle size distribution within a specific range of metal composite hydroxides as precursors, a lithium metal composite oxide (positive electrode active material) having the above-mentioned powder characteristics can be obtained.
[0023] In a first aspect of the present invention, a metal composite hydroxide is provided, which is represented by the general formula (1): Ni 1-x- y Co x Mn y M z (OH) 2+α (wherein 0.02≤x≤0.3, 0.02≤y≤0.3, 0≤z≤0.05, -0.5≤α≤0.5 are satisfied, and M is at least one element selected from Mg, Ca, Al, Si, Fe, Cr, V, Mo, W, Nb, Ti and Zr.) wherein in a particle size distribution obtained by a laser diffraction scattering method, [(D90-D10) / MV] representing a particle size dispersion index calculated from D90 and D10 and a volume average particle size (MV) is 0.80 or more; the metal composite hydroxide comprises a first particle having a core portion formed inside the particle and a shell portion formed around the core portion; the composition of the core portion is represented by the general formula (2): Ni 1-x1-y1 Co x1 Mn y1 M z1 (OH) 2+α1 (wherein 0.4<(1-x1-y1)≤0.96, 0≤z1≤0.05, -0.5≤α1≤0.5.) is satisfied; the composition of the shell is represented by the general formula (3): Ni 1-x2-y2 Co x2 Mn y2 M z2 (OH) 2+α2(Wherein, (1-x1-y1) / (1-x2-y2)>1.0, 0<(1-x2-y2)<0.6, 0≤z2≤0.05, -0.5≤α2≤0.5.) Indicates that; in a first particle having a particle size in the range of ±10% relative to the volume average particle size (MV), the shell portion has a thickness from the surface of the particle toward the center portion that is greater than 10% and less than 40% relative to the radius of the first particle.
[0024] Furthermore, the volume average particle size (MV) of the metal composite hydroxide is preferably 5 μm or more and 20 μm or less. Furthermore, it is preferred that the element M is uniformly present inside and / or on the surface of the first particle.
[0025] In a second aspect of the present invention, a method for producing a metal composite hydroxide is provided, wherein the metal composite hydroxide comprises a first particle having a core formed inside the particle and a shell formed around the core, wherein the metal composite hydroxide is represented by the general formula (1): Ni 1-x-y Co x Mn y M z (OH) 2+α wherein 0.02≤x≤0.3, 0.02≤y≤0.3, 0≤z≤0.05, -0.5≤α≤0.5 are satisfied, and M is at least one element selected from Mg, Ca, Al, Si, Fe, Cr, V, Mo, W, Nb, Ti, and Zr; the manufacturing method comprises: a first crystallization step, supplying a first raw material aqueous solution containing nickel and at least one of cobalt, manganese, and element M, and adjusting the reaction aqueous solution so that the pH value is 11.5 or more and 13.5 or less based on a liquid temperature of 25° C. to perform crystallization, thereby forming a catalyst having the general formula (2): Ni 1-x1-y1 Co x1 Mn y1 M z1 (OH) 2+α1 A core portion represented by, wherein 0.4<(1-x1-y1)≤0.96, 0≤z1≤0.05, -0.5≤α1≤0.5 are satisfied; in a second crystallization step, a second raw material aqueous solution containing a core portion is supplied to a reaction aqueous solution containing the core portion and the pH value is adjusted to 10.5 or more and 12.0 or less based on a liquid temperature of 25°C and is lower than the pH value in the first crystallization step, to form a second raw material aqueous solution having a nickel content less than that of the first raw material aqueous solution around the core portion represented by the general formula (3): Ni 1-x2-y2 Co x2 Mn y2 M z2 (OH) 2+α2The shell portion represented by (1-x1-y1) / (1-x2-y2)>1.0, 0<(1-x2-y2)<0.6, 0≤z2≤0.05, -0.5≤α2≤0.5 satisfies; the first crystallization step is carried out by a continuous crystallization method in which the precipitated product is recovered in an overflow manner, and the second crystallization step is carried out by an intermittent crystallization method; the first crystallization step and the second crystallization step are carried out by adjusting the supply amounts of the first raw aqueous solution and the second raw aqueous solution, so that in the first particle having a particle size in the range of ±10% relative to the volume average particle size (MV), the shell portion has a thickness of more than 10% and less than 40% relative to the radius of the first particle in the direction from the surface of the first particle toward the center.
[0026] In a third aspect of the present invention, there is provided a positive electrode active material for a non-aqueous electrolyte secondary battery, comprising a compound represented by the general formula (4): Li 1+a Ni 1-x-y Co x Mn y M z O 2+β A positive electrode active material for a non-aqueous electrolyte secondary battery of a lithium metal composite oxide represented by the invention, wherein -0.05≤a≤0.50, 0.02≤x≤0.3, 0.02≤y≤0.3, 0≤z≤0.05, -0.5≤β≤0.5 are satisfied, M is at least one element selected from Mg, Ca, Al, Si, Fe, Cr, V, Mo, W, Nb, Ti and Zr; in a particle size distribution obtained by a laser diffraction scattering method, [(D90-D10) / MV] representing a particle size dispersion index calculated from D90 and D10 and the above-mentioned volume average particle size (MV) is 0.80 or more; the lithium metal composite oxide comprises a second particle, the second particle having a core portion formed inside the particle and a shell portion formed around the core portion, and in the second particle, the composition of the core portion is represented by the general formula (5): Li 1+a1 Ni 1-x1-y1 Co x1 Mn y1 M z1 O 2+β1 Indicates that, -0.05≤a≤0.50, 0.4<(1-x1-y1)≤0.96, 0≤z1≤0.05, -0.5≤β1≤0.5; the composition of the shell is given by the general formula (6): Li 1+a2 Ni 1-x2-y2 Co x2 Mn y2 M z2 O 2+β2It means that -0.05≤a2≤0.50, (1-x1-y1) / (1-x2-y2)>1.0, 0<(1-x2-y2)<0.6, 0≤z2≤0.05, -0.5≤β2≤0.5 are satisfied; in the second particle having a particle size in the range of ±10% relative to the volume average particle size (MV), the shell portion has a thickness from the surface of the second particle to the center portion that is greater than 10% and less than 40% relative to the radius of the second particle.
[0027] The positive electrode active material preferably has a volume average particle size (MV) of 5 μm or more and 20 μm or less in a particle size distribution obtained by a laser diffraction scattering method, and a tap density of 2.0 g / cm 3 In addition, the element M is preferably uniformly distributed inside the lithium metal composite oxide and / or covers at least a part of the surface of the lithium metal composite oxide.
[0028] In the fourth embodiment of the present invention, a method for manufacturing a positive electrode active material for a non-aqueous electrolyte secondary battery is provided, comprising: a mixing step of mixing the above-mentioned metal composite hydroxide with a lithium compound to obtain a lithium mixture; and a calcining step of calcining the lithium mixture at a temperature of not less than 650°C and not more than 900°C in an oxidizing atmosphere.
[0029] In the fifth embodiment of the present invention, a method for manufacturing a positive electrode active material for a non-aqueous electrolyte secondary battery is provided, comprising: a heat treatment step of heat-treating the above-mentioned metal composite hydroxide; a mixing step of mixing at least one of the metal composite hydroxide and the metal composite oxide obtained after the heat treatment with a lithium compound to obtain a lithium mixture; and a calcining step of calcining the lithium mixture at a temperature of not less than 650°C and not more than 900°C in an oxidizing atmosphere.
[0030] In a sixth aspect of the present invention, there is provided a nonaqueous electrolyte secondary battery comprising a positive electrode using the above-mentioned positive electrode active material, a negative electrode, and a nonaqueous electrolyte.
[0031] Effects of the Invention
[0032] According to the present invention, a positive electrode active material and a precursor thereof which have both high charge and discharge capacity, thermal stability and weather resistance at a higher level can be obtained when used as a positive electrode material for a secondary battery. In addition, the manufacturing method of the present invention can easily manufacture the above-mentioned positive electrode active material and precursor on an industrial scale, and its industrial value is extremely great. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] [ Figure 1 ] Figure 1 This is a schematic diagram showing an example of the metal composite hydroxide according to the present embodiment.
[0034] [ Figure 2 ] Figure 2 This is a diagram showing an example of the method for producing the metal composite hydroxide according to the present embodiment.
[0035] [ Figure 3 ] Figure 3 This is a diagram showing an example of a method for producing a positive electrode active material according to this embodiment.
[0036] [ Figure 4 ] Figure 4 This is a diagram showing an example of a method for producing a positive electrode active material according to this embodiment.
[0037] [ Figure 5 ] Figure 5 This is a schematic cross-sectional view of a 2032-type button-type battery used for battery evaluation.
[0038] [ Figure 6 ] Figure 6 This is a drawing-substitute photograph showing the distribution of each metal element in the cross section of the metal composite hydroxide obtained in Example 1, obtained by surface analysis using STEM-EDX.
[0039] [ Figure 7 ] Figure 7 This is a drawing-substituting photograph showing the distribution of each metal element in the cross section of the positive electrode active material obtained in Comparative Example 8, obtained by surface analysis using STEM-EDX. DETAILED DESCRIPTION
[0040] Hereinafter, the metal composite hydroxide and its manufacturing method, the positive electrode active material for nonaqueous electrolyte secondary battery and its manufacturing method, and the nonaqueous electrolyte secondary battery according to the present embodiment are described with reference to the accompanying drawings. It should be noted that, in order to facilitate understanding of each structure, sometimes a part is emphasized or a part is simplified in the accompanying drawings to represent different actual structures, shapes, scales, etc.
[0041] 1. Metal composite hydroxides
[0042] Figure 1 : is a diagram showing an example of the metal composite hydroxide involved in this embodiment. Figure 1 As shown, the metal composite hydroxide 10 includes a first particle 11 having a core portion 11a formed inside the first particle 11 and a shell portion 11b formed around the core portion 11a. That is, the first particle 11 has a core-shell structure.
[0043] As described later, the metal composite hydroxide 10 has a high nickel ratio and a wide particle size distribution, so the secondary battery using the positive electrode active material obtained as a precursor has a very high battery capacity and energy density. Usually, the secondary battery using a positive electrode active material with a high nickel ratio and a wide particle size distribution sometimes has reduced thermal stability and weather resistance. However, the positive electrode active material using the metal composite hydroxide 10 of the present embodiment as a precursor can be high in the secondary battery. The high battery capacity and high thermal stability and weather resistance are taken into account at a high level by including the first particle 11 having a core-shell structure.
[0044] It should be noted that the metal composite hydroxide 10 (including the first particles 11) is mainly composed of secondary particles (not shown), which are formed by agglomeration of multiple primary particles. In addition, the metal composite hydroxide 10 may also contain a small amount of individual primary particles. It should be noted that in this specification, the metal composite hydroxide 10 represents all particles that constitute the metal composite hydroxide 10, including multiple first particles 11. It should be noted that the metal composite hydroxide 10 may also contain a small amount of particles other than the first particles 11. Below, the metal composite hydroxide 10 is described in detail.
[0045] [Metal composite hydroxide as a whole]
[0046] (composition)
[0047] The metal composite hydroxide 10 (as a whole) is composed of the general formula (1): Ni 1-x-y Co x Mn y M z (OH) 2+α It means that 0.02≤x≤0.3, 0.02≤y≤0.3, 0≤z≤0.05, -0.5≤α≤0.5 are satisfied, and M is at least one element selected from Mg, Ca, Al, Si, Fe, Cr, V, Mo, W, Nb, Ti and Zr.
[0048] In the above general formula (1), the value of (1-xy) representing the ratio of nickel is 0.35≤(1-xy)≤0.96, preferably 0.4≤(1-xy)≤0.96, preferably 0.55≤(1-xy)≤0.96, more preferably 0.6≤(1-xy)≤0.95, and more preferably 0.7≤(1-xy)≤0.9. When the ratio of nickel is within the above range, the secondary battery obtained by using the metal composite hydroxide 10 as a precursor of the positive electrode active material can have a high battery capacity. In particular, when the ratio of nickel is a higher value within the above range, the battery capacity (charge and discharge capacity) of the obtained secondary battery can be further improved. In addition, the value of (1-xy) can exceed 0.7. It should be noted that when the value of (1-xy) exceeds 0.96, the thermal stability of the positive electrode active material decreases.
[0049] In the above general formula (1), the value of x representing the ratio of cobalt is 0.02≤x≤0.3, preferably 0.02≤x≤0.2, more preferably 0.03≤x≤0.2, and more preferably 0.05≤x≤0.1. When the ratio of cobalt is within the above range, it helps to improve the charge and discharge cycle characteristics and output characteristics. On the other hand, when the value of x exceeds 0.3, it is difficult to increase the capacity of the secondary battery due to the relative decrease in the Ni ratio. In addition, since cobalt is expensive, from the perspective of cost, it is industrially desirable that the value of x is a lower value within the above range.
[0050] In the above general formula (1), the value of y representing the ratio of manganese is 0.02≤y≤0.3, preferably 0.05≤y≤0.25, preferably 0.10≤y≤0.20 or less, and more preferably 0.10≤y≤0.15. When the ratio of manganese is within the above range, it helps to improve thermal stability and weather resistance. On the other hand, when the value of y is less than 0.02, the thermal stability of the secondary battery using the positive electrode active material cannot be improved. On the other hand, when the value of y exceeds 0.3, the secondary battery is difficult to increase in capacity due to the relatively reduced ratio of nickel.
[0051] In addition, the metal composite hydroxide 10 may further contain an element M. As the element M, one or more selected from magnesium (Mg), calcium (Ca), aluminum (Al), silicon (Si), titanium (Ti), vanadium (V), chromium (Cr), zirconium (Zr), niobium (Nb), molybdenum (Mo), iron (Fe), and tungsten (W) may be used.
[0052] In the above general formula (1), the value of z representing the ratio of element M is 0≤z≤0.05, preferably 0.001≤z≤0.05. When the ratio of element M is within the above range, the durability and output characteristics of the secondary battery can be further improved. On the other hand, when the value of z exceeds 0.05, the battery capacity will decrease due to the reduction of metal elements participating in the Redox reaction.
[0053] It should be noted that when containing element M, element M can be crystallized together with nickel, cobalt and manganese in the crystallization process as described later, and evenly dispersed in the metal composite hydroxide 10, or can be coated on the surface of the metal composite hydroxide 10 after the crystallization process. In addition, it is also possible to coat its surface after being evenly dispersed inside the particle. In any case, the content of element M will be controlled to the above range. It should be noted that the content of nickel, cobalt, manganese and element M can be measured by ICP emission spectrometry.
[0054] (Particle size distribution of metal composite hydroxide)
[0055] For the metal composite hydroxide 10, in the particle size distribution obtained by the laser diffraction scattering method, [(D90-D10) / MV] representing the particle size dispersion index calculated from D90 and D10 and the above-mentioned volume average particle size (MV) is preferably 0.8 or more, more preferably 0.85 or more, and further preferably 0.9 or more. The particle size distribution of the positive electrode active material will be strongly affected by the metal composite hydroxide 10 as its precursor. Therefore, when [(D90-D10) / MV] of the metal composite hydroxide 10 is within the above range, the particle size distribution of the positive electrode active material with the metal composite hydroxide 10 as a precursor can be increased, the filling property of the positive electrode active material in the positive electrode can be improved, and the energy density of the secondary battery using the positive electrode active material can be further improved.
[0056] In addition, when [(D90-D10) / MV] of metal composite hydroxide 10 is too large, fine particles and coarse particles are easily present, and the secondary battery using such positive electrode active material sometimes has reduced cycle characteristics and thermal stability. Therefore, from the viewpoint of battery performance, the upper limit value of [(D90-D10) / MV] can be set to less than 1.3. As described later, the particle size distribution can be set to the above range by appropriately adjusting the crystallization conditions in the crystallization process.
[0057] It should be noted that D10 refers to the particle size when the number of particles at each particle size is accumulated from the smaller particle size side and the cumulative volume is 10% of the total volume of all particles, and D90 refers to the particle size when the number of particles is accumulated in the same way and the cumulative volume is 90% of the total volume of all particles. D10 and D90 can be obtained based on the volume cumulative value measured by a laser diffraction scattering particle size analyzer.
[0058] (Volume average particle size MV)
[0059] The average particle size of the metal composite hydroxide 10 is preferably 5 μm to 20 μm, more preferably 7 μm to 20 μm, and further preferably 7 μm to 15 μm. The average particle size of the metal composite hydroxide 10 is related to the average particle size of the positive electrode active material using the metal composite hydroxide 10 as a precursor. Therefore, when the average particle size of the metal composite hydroxide 10 is set to the above range, the average particle size of the obtained positive electrode active material can be controlled within a predetermined range. It should be noted that the average particle size of the metal composite hydroxide 10 refers to the volume average particle size (MV), which can be obtained, for example, based on the volume cumulative value measured by a laser diffraction scattering particle size analyzer.
[0060] [First Particle]
[0061] The first particle 11 contained in the metal composite hydroxide 10 includes a secondary particle formed by agglomeration of a plurality of primary particles. The first particle 11 comprises: a core portion 11a having a high nickel ratio in the center of the secondary particle, and a shell portion 11b formed around the core portion 11a and having a lower nickel ratio than the core portion 11a. It should be noted that the shape of the primary particles constituting the first particle 11 is not particularly limited, and for example, it may be a plate-like, needle-like, or other shape.
[0062] In a secondary battery, the properties of the particle surface of the positive electrode active material in contact with the atmosphere and the electrolyte have a great influence on various battery characteristics. Therefore, the first particle 11 is set to a composition that reduces the nickel ratio only in a specific range on the surface of the secondary particle, thereby having thermal stability and weather resistance. In addition, as the first particle 11 as a whole, it has a high battery capacity by having a high nickel ratio. Therefore, when the metal composite hydroxide 10 comprising the first particle 11 is used as a precursor of the positive electrode active material, a secondary battery that takes into account thermal stability, weather resistance and high battery capacity can be obtained.
[0063] (Composition of the core)
[0064] The composition of the core 11a of the first particle 11 is represented by the general formula (2): Ni 1-x1-y1 Co x1 Mn y1 M z1 (OH) 2+α1 Indicates that, among them, 0.4<(1-x1-y1)≤0.96, 0≤z1≤0.05, -0.5≤α1≤0.5 is satisfied.
[0065] In the above general formula (2), the range of (1-x1-y1) representing the ratio of nickel is 0.4<(1-x1-y1)≤0.96. From the viewpoint of high battery capacity, it is preferably 0.55≤(1-x1-y1)≤0.96, more preferably 0.6≤(1-x1-y1)≤0.96, and further preferably 0.7≤(1-x1-y1)≤0.90.
[0066] In the above general formula (2), the values of x1 and y1 indicating the ratio of cobalt to manganese are not particularly limited as long as the ratio of nickel satisfies the above range, and are selected from the ranges of 0≤x1<0.6 and 0≤y1<0.6.
[0067] In the general formula (2), the range of z1 representing the ratio of the element M is 0≤z1≤0.05, preferably 0.001≤z≤0.05. In addition, z1=0 is also possible. It should be noted that the type of element M is the same as that of the general formula (1). When the core portion 11a contains the element M, the battery characteristics can be improved.
[0068] It should be noted that the composition of the core portion 11a can be obtained, for example, by quantitative analysis of energy dispersive X-ray analysis (EDX) in cross-sectional observation using a scanning transmission electron microscope (STEM). In addition, the composition of the core portion 11a can be obtained, for example, by controlling the first crystallization step (step S1, see Figure 2 ) is adjusted to the above range by adjusting the composition of the metal component in the first raw material aqueous solution.
[0069] (Structure of the core)
[0070] In the first particle 11 having the same particle size as the volume average particle size (MV) of the metal composite hydroxide 10, the core portion 11a may have a radius R from the center of the first particle 11 with respect to the first particle 11. 11 The radius R is 60% or more and 90% or less. 11a , preferably with a radius R of 70% or more and 90% or less 11a , more preferably having a radius R of 80% or more and 90% or less 11a The radius R of the core 11a is 11a When the above range is met, the positive electrode active material using the metal composite hydroxide 10 as a precursor can have a high battery capacity. In this specification, having the same particle size as the volume average particle size (MV) means having a particle size within a range of ±10% relative to the volume average particle size (MV).
[0071] (Shell composition)
[0072] The composition of the shell portion 11b of the first particle 11 is represented by the general formula (3): Ni 1-x2-y2 Cox2 Mn y2 M z2 (OH) 2+α2 In the above formula (3), (1-x1-y1) / (1-x2-y2)>1.0, 0<(1-x2-y2)<0.6, and 0≤z2≤0.05 are satisfied.
[0073] In the above general formula (3), the value of (1-x2-y2) representing the ratio of nickel in the shell 11b satisfies (1-x1-y1) / (1-x2-y2)>1.0, and 0<(1-x2-y2)<0.6. That is, the nickel ratio of the shell 11b is lower than the nickel ratio of the core 11a, and contains nickel in an amount of less than 60 mol% relative to the number of atoms (number of moles) of all metal elements other than the element M. When the nickel ratio of the shell 11b is low, a positive electrode active material having excellent thermal stability and weather resistance can be obtained. In addition, from the viewpoint of high battery capacity, the nickel ratio is preferably a high value within the above range.
[0074] In the above general formula (3), the value of x2 representing the content of cobalt is not particularly limited as long as it satisfies the above formula, for example, 0≤x2<1.0, preferably 0.05≤x2≤0.6, and more preferably 0.05≤x2≤0.5. When the content of cobalt (x2) is within the above range, the thermal stability and cycle characteristics of the secondary battery using the metal composite hydroxide 10 as a precursor of the positive electrode active material are more excellent. In addition, from the viewpoint of further improving thermal stability and weather resistance, the value of x2 can also be 0.05≤x2≤0.3.
[0075] In the above general formula (3), the value of y2 representing the manganese content is not particularly limited as long as it satisfies the above formula, for example, 0≤y2<1.0, preferably 0.05≤y2≤0.6, and more preferably 0.05≤y2≤0.5. When the manganese content (y2) is within the above range, a secondary battery using the metal composite hydroxide 10 as a precursor of a positive electrode active material can have high thermal stability and weather resistance. In addition, from the viewpoint of further improving thermal stability and cycle characteristics, the value of y2 can be 0.05≤y2≤0.3.
[0076] In the general formula (3), z2 indicating the ratio of the element M is in the range of 0≤z2≤0.05, and z2=0. The type of the element M is the same as that in the general formula (1). When the shell portion 11b contains the element M, the battery characteristics can be improved.
[0077] It should be noted that the composition of the shell portion 11b can be obtained, for example, by quantitative analysis of energy dispersive X-ray analysis (EDX) in cross-sectional observation using a scanning transmission electron microscope (STEM). It should be noted that the shell portion 11b of the first particle 11 may have a composition gradient, for example, on the surface side of the first particle 11 and on the inner side in contact with the core portion 11a, but it is preferred that the shell portion 11b has a uniform composition as a whole. Here, the shell portion 11b having a uniform composition as a whole means, for example, Figure 6 As shown in FIG. 1 , when the cross section of the first particle 11 is analyzed by STEM-EDX, no uneven distribution of the metal elements is observed in the entire shell portion 11b. In addition, regarding the composition of the shell portion 11b, for example, as described later, the second crystallization step (step S2, see Figure 2 ) is adjusted to the above range by adjusting the composition of the metal component in the second raw material aqueous solution.
[0078] (Structure of the shell)
[0079] In the first particle 11 having the same particle size as the volume average particle size (MV) of the metal composite hydroxide 10 (i.e., a particle size within a range of ±10% relative to the MV), the thickness t of the shell portion 11b in the direction from the particle surface toward the center portion C is 1000 mm / s relative to the radius R of the first particle 11. 11 It is not less than 10% and not more than 40%, preferably not less than 10% and not more than 30%, and more preferably not less than 10% and not more than 20%. When the thickness t of the shell portion 11b is within the above range, the thermal stability and weather resistance of the secondary battery using the positive electrode active material obtained using the metal composite hydroxide 10 as a precursor are excellent. In addition, when the upper limit of the thickness t of the shell portion 11b is within the above range, the volume of the core portion 11a with a high nickel ratio can be increased, and the secondary battery using the positive electrode active material obtained using the metal composite hydroxide 10 as a precursor has a high battery capacity. It should be noted that the thickness t of the shell portion 11b and the radius R 11 This is a value measured by observing a cross section of the metal composite hydroxide 10 using a scanning transmission electron microscope (STEM) or the like.
[0080] The thickness t of the shell portion 11b can be, for example, 0.2 μm to 2.0 μm, preferably more than 0.5 μm and 1.6 μm or less, and more preferably 0.6 μm to 1.0 μm, in the direction from the surface of the first particle 11 to the center portion C. When the lower limit of the thickness of the shell portion 11b is within the above range, a positive electrode active material having excellent thermal stability and weather resistance can be obtained.
[0081] 2. Method for producing metal composite hydroxide
[0082] Figure 2: is a diagram showing an example of a method for producing a metal composite hydroxide according to the present embodiment. The method for producing a metal composite hydroxide according to the present embodiment comprises a crystallization step (step S10): a metal composite hydroxide comprising first particles having a core-shell structure is produced by a crystallization reaction. The obtained metal composite hydroxide is represented by the general formula (1): Ni 1-x-y Co x Mn y M z (OH) 2+α Indicates that, wherein 0.02≤x≤0.3, 0.02≤y≤0.3, 0≤z≤0.05, -0.5≤α≤0.5 are satisfied, and M is at least one element selected from Mg, Ca, Al, Si, Fe, Cr, V, Mo, W, Nb, Ti, and Zr. By the manufacturing method involved in this embodiment, the above-mentioned metal composite hydroxide 10 can be easily manufactured on an industrial scale. It should be noted that the above-mentioned metal composite hydroxide 10 can also be manufactured by the following method in the manufacturing method involved in this embodiment.
[0083] The manufacturing method involved in this embodiment is as described below, and clearly divides the crystallization process (step S10) into two stages: a first crystallization process (step S1) that mainly forms the core portion of the first particle and a second crystallization process (step S2) that mainly forms the shell portion of the first particle. By adjusting the crystallization conditions in each process, the above-mentioned metal composite hydroxide 10 can be easily obtained.
[0084] (1) Crystallization process
[0085] In the method for producing the metal composite hydroxide of the present embodiment, Figure 2 As shown, it comprises: a first crystallization step (step S1), supplying a first raw material aqueous solution containing nickel and at least one of cobalt, manganese and the above-mentioned element M to a reaction tank, adjusting the pH value of the reaction aqueous solution in the reaction tank to a specific range, and performing crystallization to form a core portion; and a second crystallization step (step S2), supplying a second raw material aqueous solution containing at least one of nickel, cobalt and manganese and an arbitrary element M and having a less nickel content than the first raw material aqueous solution to the reaction aqueous solution containing the core portion whose pH value is adjusted to a specific range, and performing crystallization to form a shell portion.
[0086] In addition, as a crystallization method, a continuous crystallization method is preferably used in the first crystallization step (step S1). Thus, a positive electrode active material having a wide particle size distribution and high filling property can be obtained. In addition, an intermittent crystallization method is preferably used in the second crystallization step (step S2). Thus, a shell structure having a composition with a low nickel ratio can also be formed for the first particle having a smaller particle size, and a positive electrode active material with improved thermal stability can be obtained. Below, each process is described.
[0087] [First Crystallization Step (Step S1)]
[0088] In the first crystallization step (step S1), a first raw material aqueous solution containing nickel and at least one of cobalt, manganese and the above-mentioned element M is supplied to a reaction tank, and the pH value of the reaction aqueous solution is adjusted to a pH range of 11.5 to 13.5 to perform crystallization to form a core portion. The composition of the core portion is represented by the general formula (2): Ni 1-x1-y1 Co x1 Mn y1 M z1 (OH) 2+α1 It means that 0.4<(1-x1-y1)≤0.96, 0≤z1≤0.05, and -0.5≤α1≤0.5 are satisfied. A suitable example of the first crystallization step (step S1) is described below.
[0089] First, an alkaline aqueous solution is supplied to a reaction tank and mixed to prepare a pre-reaction aqueous solution having a pH value of 11.5 to 13.5 as measured at a liquid temperature of 25° C. In addition, the ammonium ion concentration of the pre-reaction aqueous solution can be adjusted to, for example, a range of 3 g / L to 25 g / L. It should be noted that the pH value of the pre-reaction aqueous solution can be measured by a pH meter.
[0090] Next, the first raw aqueous solution is supplied while stirring the pre-reaction aqueous solution. Thus, a reaction aqueous solution in the first crystallization step (a reaction aqueous solution for core crystallization) is formed in the reaction tank. Since the pH value of the reaction aqueous solution is in the above range, nucleation and nucleus growth occur simultaneously in the reaction tank. It should be noted that in the first crystallization step, as the particles are generated, the pH value and ammonium ion concentration of the reaction aqueous solution will change. Therefore, an alkaline aqueous solution and an ammonia aqueous solution should be supplied in a timely manner and controlled so that the pH value of the liquid in the reaction tank is maintained in the range of pH 11.5 to 13.5 based on a liquid temperature of 25°C.
[0091] In the first crystallization step, for example, the first raw material aqueous solution, the alkaline aqueous solution, and the aqueous solution containing the ammonium ion donor are continuously supplied to the reaction aqueous solution, so that new nuclei can be continuously generated and the particles can continue to grow. Moreover, when a predetermined amount of the first raw material aqueous solution is added, the first crystallization step is terminated.
[0092] The pH value of the reaction aqueous solution in the first crystallization step (the reaction aqueous solution for core crystallization) is controlled to be in the range of 11.5 to 13.5, preferably 12.0 to 13.0, based on the liquid temperature of 25°C. When the pH is in the above range, the excessive generation of the core can be suppressed, and the particle size distribution of the particles (mainly the core of the first particle) generated in the first crystallization step can be stably expanded. When the pH value is less than 11.5, the solubility of the metal ions increases, so the speed of the crystallization reaction slows down, and the metal ions will remain in the reaction aqueous solution, resulting in the composition of the obtained metal composite hydroxide sometimes deviating from the target value. In addition, when the pH value exceeds 13.5, the nucleus generation occurs preferentially compared to the growth of the nucleus (particle), so the particle size of the obtained metal composite hydroxide is small and tends to become uneven. Furthermore, when the pH value exceeds 14.0, the generated core becomes too fine, so sometimes there is a problem of gelation of the reaction aqueous solution. It should be noted that the fluctuation range of the pH value in the crystallization reaction is preferably controlled within ±0.2. When the pH value in the crystallization reaction fluctuates widely, the ratio between the amount of nucleation and the growth of particles becomes unstable, and it becomes difficult to obtain a metal composite hydroxide having a stable particle size distribution.
[0093] [Second Crystallization Step (Step S2)]
[0094] In the second crystallization step (step S2), a second raw material aqueous solution having a lower nickel content than the first raw material aqueous solution is supplied to the reaction aqueous solution whose pH value is adjusted to a range of 10.5 to 12.0, thereby obtaining first particles having a shell formed around the core. The composition of the shell is given by the general formula (3): Ni 1-x2-y2 Co x2 Mn y2 M z2+α2 (OH)2 represents, wherein (1-x1-y1) / (1-x2-y2)>1.0, 0<(1-x2-y2)<0.6, 0≤z2≤0.05, -0.5≤α2≤0.5. A suitable example of the second crystallization step (step S2) is described below.
[0095] First, after the first crystallization step (step S1), the pH value of the reaction aqueous solution containing the core portion in the reaction tank is adjusted to 10.5 or more and 12.0 or less based on a liquid temperature of 25°C, to form a reaction aqueous solution in the second crystallization step (a reaction aqueous solution for shell crystallization). The pH value of the reaction aqueous solution can also be adjusted by stopping the supply of an alkaline aqueous solution, but in order to stably obtain a metal composite hydroxide with a particle size distribution maintained, it is preferred to temporarily stop all aqueous solution supplies to adjust the pH value. Specifically, it is preferred that after stopping all aqueous solution supplies, the pH value is adjusted by supplying an inorganic acid of the same type as the acid constituting the metal compound as a raw material to the reaction aqueous solution.
[0096] Next, the second raw material aqueous solution is supplied while stirring the reaction aqueous solution. At this time, since the pH value of the reaction aqueous solution is within the above range, new nuclei are hardly generated, but nuclei (particles) grow to form a metal composite hydroxide that maintains the particle size distribution width of the particles obtained by the first crystallization step. It should be noted that in the second crystallization step, as the particles grow, the pH value and ammonium ion concentration of the aqueous solution for particle growth will also change, so it is necessary to supply an alkaline aqueous solution and an ammonia solution in a timely manner to maintain the pH value and ammonium ion concentration within the above range.
[0097] The pH value of the reaction aqueous solution in the second crystallization step (reaction aqueous solution for shell crystallization) is controlled to be in the range of 10.5 to 12.0, preferably 11.0 to 12.0, based on a liquid temperature of 25°C. When the pH is in the above range, the excessive generation of new nuclei can be suppressed, and the particle size distribution of all particles generated in the second crystallization step (step S2) can be stably expanded. On the other hand, when the pH value is less than 10.5, the ammonium ion concentration will rise, and the solubility of metal ions will increase, so not only the speed of the crystallization reaction will slow down, but also the amount of metal ions remaining in the reaction aqueous solution will increase, and productivity will sometimes deteriorate. In addition, when the pH value exceeds 12.0, the amount of nuclei generated in the particle growth process will increase, the particle size of the obtained metal composite hydroxide will become uneven, and the particle size distribution will easily fall outside the appropriate range. It should be noted that the fluctuation range of the pH value in the crystallization reaction is preferably controlled within ±0.2. When the fluctuation range of the pH value is large, the ratio of the amount of nuclei generated and the particle growth will become unstable, and it is difficult to obtain a metal composite hydroxide with a stable particle size distribution.
[0098] In addition, the pH value of the reaction aqueous solution (reaction aqueous solution for shell crystallization) in the second crystallization step (step S2) is preferably controlled to a value lower than the pH value of the reaction aqueous solution (reaction aqueous solution for core crystallization) in the first crystallization step (step S1). From the viewpoint of clearly separating nucleation and particle growth and obtaining a metal composite hydroxide with a stable particle size distribution, the pH value of the reaction aqueous solution in the second crystallization step (step S2) is preferably lower than the pH value of the reaction aqueous solution in the first crystallization step by 0.5 or more, and more preferably lower by 0.9 or more.
[0099] It should be noted that when the pH value of the reaction aqueous solution in the first crystallization step (step S1) or the second crystallization step (step S2) is in the range of 11.5 to 12.0, since it is a boundary condition for nucleation and nucleus growth, it can be set as a condition in which either nucleus generation or nucleus growth occurs first, depending on whether there is a nucleus in the reaction aqueous solution. That is, after the pH value of the first crystallization step is adjusted to be higher than 12.0 so that a large number of nuclei are generated, when the pH value of the second crystallization step is adjusted to 11.5 to 12.0, since there are a large number of nuclei in the reaction aqueous solution, particle growth will occur first, and a metal composite hydroxide with a narrow particle size distribution can be obtained. On the other hand, when the pH value of the first crystallization step (step S1) is adjusted to 11.5 to 12.0, since there is no nucleus to be grown in the reaction aqueous solution, nucleus generation will occur first, and the pH value of the second crystallization step (step S2) is adjusted to be lower than the pH value of the reaction aqueous solution of the first crystallization step, so that the generated nucleus will grow, and a good metal composite hydroxide can be obtained.
[0100] In addition, the period of switching from the first crystallization step (step S1) to the second crystallization step (step S2) can be adjusted so that the core 11a and the shell 11b of the above-mentioned first particle 11 reach a predetermined thickness. For example, in the first crystallization step (step S1), after adding more than 60 mol% and less than 90 mol%, preferably more than 65 mol% and less than 80 mol%, based on the total amount of metal salts in the raw aqueous solution (including the first raw aqueous solution and the second raw aqueous solution) supplied in the entire crystallization step (step S10), switching to the second crystallization step (step S2) can be performed.
[0101] [Metal composite hydroxide]
[0102] In the second crystallization step (step S2), the obtained metal composite hydroxide comprises a first particle having a core formed inside the particle and a shell formed around the core. Here, the particle size of the metal composite hydroxide (as a whole) can be controlled by the supply amount of the raw material aqueous solution in the first crystallization step (step S1) and the second crystallization step (step S2), the crystallization time, the pH value of the reaction aqueous solution, etc. For example, by performing the first crystallization step (step S1) in a reaction aqueous solution having a high pH value, the amount of nuclei generated can be increased and the particle size of the obtained metal composite hydroxide can be reduced. On the contrary, by suppressing the amount of nuclei generated in the first crystallization step (step S1), the particle size of the obtained metal composite hydroxide can be increased. Below, suitable examples of other conditions other than those mentioned above in the crystallization step involved in the present embodiment are described.
[0103] (Raw aqueous solution)
[0104] The first and second raw material aqueous solutions are modulated by dissolving a compound containing a transition metal (Ni, Co, Mn, or any M) as a raw material for the first and second crystallization steps in water. In the crystallization step, the ratio of the metal elements in the raw material aqueous solution is roughly the same as the composition ratio of the obtained metal composite hydroxide. Therefore, the raw material aqueous solution used can be appropriately adjusted according to the composition of the target metal composite hydroxide.
[0105] In the manufacturing method of this embodiment, the ratio of metal elements in the raw aqueous solution (as a whole) used in the crystallization reaction is basically consistent with the composition ratio of metals in the metal composite hydroxide represented by the above-mentioned general formula (1), and therefore can be adjusted to Ni:Mn:Co:M=(1-xy):x:y:z (satisfying 0.02≤x≤0.3, 0.02≤y≤0.3, 0≤z≤0.05.).
[0106] The ratio of the metal elements in the first raw material aqueous solution can be adjusted to, for example, Ni:Co:Mn:M=(1-x1-z1):x1:y1:z1, wherein 0.4<(1-x1-y1)≤0.96, 0≤z1≤0.05 are satisfied. From the viewpoint of high battery capacity, (1-x1-y1) representing the ratio of Ni in the first raw material aqueous solution is preferably 0.55≤(1-x1-y1)≤0.96, more preferably 0.6≤(1-x1-y1)≤0.96, and further preferably 0.7≤(1-x1-y1)≤0.90.
[0107] The ratio of metal elements in the second raw aqueous solution can be adjusted to, for example, Ni:Co:Mn:M=(1-x2-z2):x2:y2:z2, wherein (1-x1-y1) / (1-x2-y2)>1.0, 0<(1-x2-y2)<0.6). In addition, (1-x2-y2) representing the ratio of Ni in the second raw aqueous solution preferably satisfies 0<(1-x2-y2)<0.5. When the ratio of Ni is within the above range, when the positive electrode active material using the obtained metal composite hydroxide as a precursor is used in a secondary battery, the thermal stability and weather resistance are excellent.
[0108] In addition, from the viewpoint of further improving the output characteristics and cycle characteristics of the secondary battery, x2 representing the content of Co in the second raw aqueous solution is, for example, 0≤x2<1.0, preferably 0.05≤x2≤0.6, and more preferably 0.05≤x2≤0.5. In addition, from the viewpoint of further improving the thermal stability and short-circuit resistance of the secondary battery, y2 representing the content of Mn is, for example, 0≤y2<1.0, preferably 0.05≤y2≤0.6, and more preferably 0.05≤y2≤0.5.
[0109] There is no particular restriction on the compounds of transition metal elements (Ni, Co, Mn, or any M) used in the preparation of the first and second raw aqueous solutions. From the perspective of ease of operation, it is preferred to use water-soluble nitrates, sulfates, and hydrochlorides. From the perspective of cost and prevention of halogen mixing, it is particularly preferred to use sulfates.
[0110] In addition, when at least one of the first and second raw material aqueous solutions contains element M (M is one or more additional elements selected from Mg, Ca, Al, Ti, V, Cr, Zr, Nb, Mo, Hf, Fe and W), the compound containing M is preferably a water-soluble compound. For example, magnesium sulfate, calcium sulfate, aluminum sulfate, titanium sulfate, ammonium peroxytitanate, potassium titanium oxalate, vanadium sulfate, ammonium vanadate, chromium sulfate, potassium chromate, zirconium sulfate, niobium oxalate, ammonium molybdate, hafnium sulfate, iron sulfate, sodium tungstate, ammonium tungstate, etc. can be appropriately used.
[0111] The concentration of each of the first and second raw aqueous solutions is preferably 1 mol / L or more and 2.6 mol / L or less, and more preferably 1.5 mol / L or more and 2.2 mol / L or less, based on the total amount of the metal compound. When the concentration of the first and second raw aqueous solutions is less than 1 mol / L, the amount of crystallization per unit reaction tank decreases, and thus productivity sometimes decreases. On the other hand, when the concentration of the first and second raw aqueous solutions exceeds 2.6 mol / L, it will exceed the saturation concentration at room temperature, and thus the crystals of each metal compound will precipitate again, and there will be concerns about clogging the piping, etc.
[0112] It should be noted that the first and second raw material aqueous solutions may use one raw material aqueous solution or multiple raw material aqueous solutions. For example, when multiple compounds are mixed in the first crystallization step, when a metal compound that reacts to generate a compound other than the target compound is used in the raw material for the crystallization reaction, the raw material aqueous solutions containing the metal compound can be respectively modulated, and the raw material aqueous solutions containing each metal compound in a predetermined ratio are supplied to the reaction tank in a predetermined ratio, so that the total concentration of the first raw material aqueous solution as a whole is within the above range.
[0113] In addition, the supply amount of the first raw material aqueous solution is set to: at the end of the first crystallization step, the concentration of the product (mainly the core of the first particle) in the reaction aqueous solution is preferably 30 g / L or more and 200 g / L or less, and more preferably 80 g / L or more and 150 g / L or less. When the concentration of the product is less than 30 g / L, the aggregation of the primary particles constituting the first particles may sometimes become insufficient. On the other hand, when the metal compound aqueous solution is separately modulated and exceeds 200 g / L, the metal salt aqueous solution for nucleation or the metal salt aqueous solution for particle growth cannot be fully diffused in the reaction tank, and sometimes there may be a situation where the particle growth is uneven.
[0114] In addition, in the second crystallization process, due to the low pH value of the reaction aqueous solution, even if the product concentration in the shell crystallization aqueous solution is denser than the first crystallization process (core formation), particle growth is also easy to occur. At the end of the second crystallization process, the product concentration in the reaction aqueous solution for shell crystallization is preferably 30g / L or more and 1000g / L or less, more preferably 80g / L or more and 800g / L or less, more preferably 80g / L or more and 500g / L or less. When the concentration of the product is less than 30g / L, sometimes there is a situation where the aggregation of primary particles becomes insufficient. On the other hand, if it exceeds 500g / L, in the reaction tank, the metal salt aqueous solution in the reaction aqueous solution cannot be fully diffused, and sometimes there is a situation where particle growth produces unevenness.
[0115] (Alkaline aqueous solution)
[0116] The alkaline aqueous solution for adjusting the pH value in the reaction aqueous solution is not particularly limited, and the aqueous solution of common alkali metal hydroxides such as sodium hydroxide and potassium hydroxide can be used. It should be noted that alkali metal hydroxide can also be directly added in the reaction aqueous solution, but from the ease of pH control, it is preferably added in the form of an aqueous solution. In this case, the concentration of the aqueous solution of alkali metal hydroxide is preferably set to 20 mass %~50 mass %, more preferably set to 20 mass %~30 mass %. By limiting the concentration of the alkali metal aqueous solution to such a range, the amount of solvent (water) supplied to the reaction system can be suppressed, and the local increase in the pH value at the addition position is prevented, so that the particle size distribution of the composite hydroxide particles can be easily controlled.
[0117] It should be noted that there is no particular limitation on the method for supplying the aqueous alkali solution as long as the pH of the aqueous reaction solution does not increase locally and is maintained within a predetermined range. For example, the aqueous reaction solution may be supplied by a flow-controllable pump such as a metering pump while the aqueous reaction solution is fully stirred.
[0118] (Ammonium ion concentration)
[0119] The ammonium ion concentration in the reaction aqueous solution preferably remains at a constant value in the scope of more than 3g / L and less than 25g / L, more preferably more than 5g / L and less than 20g / L. Because ammonium ion plays a role as complexing agent in the reaction aqueous solution, therefore, when ammonium ion concentration is less than 3g / L, the solubility of metal ion can not be maintained as certain, in addition, the reaction aqueous solution is easy to gelation, is difficult to obtain the composite hydroxide particles of shape, particle diameter neat. On the other hand, if ammonium ion concentration exceeds 25g / L, the solubility of metal ion becomes excessive, thereby the metal ion amount remaining in the reaction aqueous solution will increase, becomes the cause of composition inequality.
[0120] It should be noted that if the ammonium ion concentration changes in the crystallization reaction, the solubility of the metal ion can change, and the particle of the metal composite hydroxide of stable particle size distribution can not be formed. Therefore, in the whole process of the first crystallization step (core formation) and the second crystallization step (shell formation), the fluctuation range of the ammonium ion concentration is preferably controlled to a certain range, specifically, preferably controlled to the fluctuation range of ± 5g / L.
[0121] The aqueous solution containing the ammonium ion donor is also not particularly limited, for example, aqueous ammonia or aqueous solutions of ammonium sulfate, ammonium chloride, ammonium carbonate or ammonium fluoride can be used. When using aqueous ammonia as the ammonium ion donor, its concentration is preferably 20% to 30% by mass, more preferably 22% to 28% by mass. When the concentration of aqueous ammonia is within the above range, the loss of ammonia due to volatilization can be minimized, thereby achieving an increase in production efficiency. It should be noted that the method for supplying the aqueous solution containing the ammonium ion donor is also the same as that of the alkaline aqueous solution, and can be supplied by a pump capable of controlling the flow rate.
[0122] (Reaction temperature)
[0123] The temperature of the reaction aqueous solution (reaction temperature) is preferably controlled to be above 20°C throughout the entire process of the first and second crystallization steps, and more preferably in the range of above 20°C and below 60°C. When the reaction temperature is less than 20°C, since the solubility of the reaction aqueous solution becomes low, nucleation is likely to occur, and the control of the average particle size and particle size distribution of the obtained composite hydroxide particles becomes difficult. It should be noted that there is no particular restriction on the upper limit of the reaction temperature, but when it exceeds 60°C, the volatilization of ammonia will be promoted. In order to control the ammonium ions in the reaction aqueous solution to a certain range, the amount of the aqueous solution containing the ammonium ion donor supplied will increase, and the production cost will increase.
[0124] (Reaction atmosphere)
[0125] The reaction atmosphere in the first and second crystallization steps is not particularly limited, and is preferably controlled to be a non-oxidizing atmosphere. Specifically, it can be controlled to be a mixed atmosphere of oxygen and an inert gas, so that the oxygen concentration in the reaction atmosphere is, for example, 5% by volume or less, preferably 2% by volume or less. Thus, it is possible to suppress unnecessary oxidation, and it is possible to grow the nuclei generated in the first crystallization step (step S1) to a certain range.
[0126] (Coating process)
[0127] The method for producing the metal composite hydroxide of the present embodiment may further include adding a compound containing any element M to the raw aqueous solution. When the raw aqueous solution contains the element M, a metal composite hydroxide in which the element M is uniformly dispersed inside the particles can be obtained. In addition, after the second crystallization step, a coating step of coating the surface of the metal composite hydroxide with a compound containing the element M may be performed. When coating the element M, the effect caused by adding the element M can be obtained with a smaller addition amount.
[0128] The coating method is not particularly limited as long as the metal composite hydroxide can be coated by the compound containing element M. For example, after the metal composite hydroxide is slurried and its pH value is controlled within a predetermined range, an aqueous solution (coating aqueous solution) in which a compound containing element M is dissolved is added to precipitate the compound containing element M on the surface of the metal composite hydroxide, thereby obtaining composite hydroxide particles coated by the compound containing element M. In this case, an alkoxide solution of element M can also be added to the slurried metal composite hydroxide instead of the coating aqueous solution. In addition, the metal composite hydroxide can also be coated by blowing an aqueous solution or slurry dissolved with a compound containing element M and drying it without slurrying the metal composite hydroxide. Furthermore, it is also possible to coat by spraying a slurry obtained by suspending a metal composite hydroxide and a compound containing element M, or by mixing a metal composite hydroxide with a compound containing element M in a solid phase method.
[0129] It should be noted that when the surface of the metal composite hydroxide is coated by element M, the composition of the raw material aqueous solution and the coating aqueous solution can be appropriately adjusted so that the composition of the metal composite hydroxide after coating is consistent with the composition of the target metal composite hydroxide. In addition, the coating process can also be performed on the heat-treated particles after the metal composite hydroxide is heat-treated. In addition, when coated by element M, the thickness of the coating layer can be appropriately adjusted within the range of not hindering the effect of the present invention.
[0130] (Manufacturing equipment)
[0131] In the first crystallization step (step S1) involved in the present embodiment, it is preferred to use a continuous crystallization device that recovers the precipitated (crystallized) product in an overflow manner. When using a continuous crystallization device, since the grown particles are recovered simultaneously with the overflow liquid before excessive particle growth, it is easy to obtain composite hydroxide particles that stably have a wide particle size distribution.
[0132] On the other hand, in the second crystallization step (step S2), it is preferred to use an intermittent crystallization device that does not recycle the precipitated product before the crystallization reaction ends. If it is such a crystallization device, unlike a continuous crystallization device that recycles the product in an overflow manner, the growing particles will not be recovered simultaneously with the overflow liquid, so it is possible to cover the shell portion on the particle (core portion) surface while maintaining the particle size distribution of the metal composite hydroxide obtained in the first crystallization step (core portion formation).
[0133] 3. Positive electrode active material for non-aqueous electrolyte secondary batteries
[0134] The positive electrode active material for a non-aqueous electrolyte secondary battery according to the present embodiment (hereinafter also referred to as “positive electrode active material”) contains a compound represented by the general formula (4): Li 1+a Ni 1-x-y Co x Mn y M z O 2+β A lithium metal composite oxide represented by a lithium metal composite oxide, wherein -0.05≤a≤0.50, 0.02≤x≤0.3, 0.02≤y≤0.3, 0≤z≤0.05, -0.5≤β≤0.5 are satisfied, and M is at least one element selected from Mg, Ca, Al, Si, Fe, Cr, V, Mo, W, Nb, Ti and Zr.
[0135] As described later, the positive electrode active material of the present embodiment can be manufactured using the above-mentioned metal composite hydroxide 10 as a precursor. The lithium metal composite oxide includes a second particle having a core portion formed inside the particle and a shell portion formed around the core portion. The second particle can be obtained using the above-mentioned first particle 11 as a precursor. The positive electrode active material of the present embodiment contains a second particle having a core-shell structure, so that when used as a positive electrode of a secondary battery, it can take into account high battery capacity and high thermal stability and weather resistance at a high level.
[0136] It should be noted that the positive electrode active material is composed of secondary particles formed by the aggregation of multiple primary particles. In addition, within the scope of not hindering the effect of the present invention, the positive electrode active material may also contain a small amount of individual primary particles and other lithium metal composite oxide particles. It should be noted that in this specification, the positive electrode active material refers to all particles that constitute the positive electrode active material, including lithium metal composite oxides (including second particles) and particles other than these. Below, the positive electrode active material is described in detail.
[0137] [Composition of lithium metal composite oxide]
[0138] The composition (overall) of the lithium metal composite oxide according to this embodiment is represented by the general formula (4): Li 1+a Ni 1-x-y Co x Mn y M z O 2+β It means that -0.05≤a≤0.50, 0.02≤x≤0.3, 0.02≤y≤0.3, 0≤z≤0.05, -0.5≤β≤0.5 are satisfied, and M is at least one element selected from Mg, Ca, Al, Si, Fe, Cr, V, Mo, W, Nb, Ti and Zr.
[0139] In the above general formula (4), the value of a representing the excess amount of lithium (Li) satisfies -0.05≤a≤0.50, preferably 0≤a≤0.20, and more preferably 0≤a≤0.10. When the excess amount of lithium is within the above range, the output characteristics and battery capacity of the secondary battery using the positive electrode active material as the positive electrode material can be improved. In contrast, when the value of a is less than -0.05, the positive electrode resistance of the secondary battery increases, thereby failing to improve the output characteristics. On the other hand, when the value of a exceeds 0.50, not only the initial charge and discharge capacity decreases, but the positive electrode resistance sometimes also increases. In addition, the value of a can be 0≤a<0.15, or 0≤a<1.03.
[0140] It should be noted that, in the lithium metal composite oxide represented by the above general formula (4), the composition range and preferred range of nickel, manganese, cobalt and element M constituting it can be the same as that of the metal composite hydroxide 10 represented by the above general formula (1). Therefore, the description of these matters is omitted here. It should be noted that the content of lithium, nickel, cobalt, manganese and element M can be measured by ICP emission spectrometry.
[0141] [Particle size distribution of positive electrode active material]
[0142] In the particle size distribution obtained by the laser diffraction scattering method of the positive electrode active material, [(D90-D10) / MV] representing the particle size dispersion index calculated by D90 and D10 and the above-mentioned volume average particle size (MV) is preferably 0.80 or more, more preferably 0.85 or more, and further preferably 0.90 or more. When [(D90-D10) / MV] of the positive electrode active material is within the above range, the particle size distribution of the positive electrode active material can be expanded, the filling property of the positive electrode active material in the positive electrode can be improved, and the energy density of the secondary battery using the positive electrode active material can be further improved.
[0143] In addition, when [(D90-D10) / MV] of the positive electrode active material is too large, fine particles and coarse particles are prone to exist, and the cycle characteristics and thermal stability of the secondary battery using such a positive electrode active material are sometimes reduced. Therefore, from the perspective of battery performance, the upper limit value of [(D90-D10) / MV] can be set to less than 1.3. The particle size distribution of the positive electrode active material can be set to the above range, for example, by adjusting the particle size distribution of the metal composite hydroxide used as a precursor to the above range. It should be noted that the meaning of D10 and D90 in the index [(D90-D10) / MV] representing the width of the particle size distribution and their method of obtaining are the same as those of the above-mentioned metal composite hydroxide 10, so the description is omitted here.
[0144] [Average particle size of positive electrode active material]
[0145] The average particle size of the positive electrode active material is preferably 5 μm to 20 μm, more preferably 7 μm to 20 μm, and further preferably 7 μm to 15 μm. When the average particle size of the positive electrode active material is within the above range, it can not only increase the battery capacity per unit volume of the secondary battery using the positive electrode active material, but also improve thermal stability and output characteristics. In contrast, when the average particle size is less than 5 μm, the filling property of the positive electrode active material will decrease, and it will be difficult to increase the battery capacity per unit volume. On the other hand, when the average particle size exceeds 20 μm, the reaction area of the positive electrode active material will decrease, and the interface between the positive electrode active material and the electrolyte in the secondary battery will decrease, making it difficult to improve the output characteristics. It should be noted that the average particle size of the positive electrode active material refers to the volume average particle size (MV), which can be obtained, for example, based on the volume cumulative value measured by a laser diffraction scattering particle size analyzer.
[0146] (Composition of the core)
[0147] The composition of the core of the lithium metal composite oxide (second particle) is represented by the general formula (5): Li 1+a1 Ni 1-x1- y1 Co x1 Mn y1 M z1 O 2+β1 It means that -0.05≤a1≤0.50, 0.4<(1-x1-y1)≤0.96, 0≤z1≤0.05, -0.5≤β1≤0.5 are satisfied.
[0148] In the above general formula (5), the range of a representing the excess amount of Li can be the same as that of the above general formula (4). In addition, in the above general formula (5), the values of (1-x1-y1), x1, y1 and z1 representing the ratio of Ni, Co, Mn and element M are the same as those of the core 11a of the metal composite hydroxide 10 represented by the above general formula (2).
[0149] It should be noted that the composition of the core of the lithium metal composite oxide (second particle) can be obtained, for example, by quantitative analysis of energy dispersive X-ray analysis (EDX) in cross-sectional observation using a scanning transmission electron microscope (STEM). In addition, the composition of the metal element other than lithium in the core of the second particle can be adjusted to the above range by, for example, setting the composition of the core of the metal composite hydroxide 10 used as a precursor to the range of the above general formula (2), and the composition of lithium in the core of the second particle can be adjusted to the above range by setting the mixing ratio of the precursor and the lithium compound to the range described later.
[0150] (Structure of the core)
[0151] In the second particle having the same particle size as the volume average particle size MV of the positive electrode active material (i.e., a particle size in the range of ±10% relative to MV), the core portion may have a radius of 60% to 90% relative to the radius of the second particle from the center of the second particle, preferably a radius of 60% to 90%, preferably a radius of 70% to 90%, and more preferably a radius of 80% to 90%. When the radius of the core portion is within the above range, the positive electrode active material can have a high battery capacity.
[0152] (Shell composition)
[0153] The composition of the shell of the lithium metal composite oxide (second particle) is represented by the general formula (6): Li 1+a2 Ni 1-x2- y2 Co x2 Mn y2 M z2 O 2+β2 It means that -0.05≤a2≤0.50, (1-x1-y1) / (1-x2-y2)>1.0, 0<(1-x2-y2)<0.6, 0≤z2≤0.05, -0.5≤β2≤0.5.
[0154] In the above general formula (6), the range of a representing the excess amount of Li can be the same as that of the above general formula (4). In addition, in the above general formula (6), the values of (1-x2-y2), x2, y2 and z2 representing the ratio of Ni, Co, Mn and element M are the same as those of the shell 11b of the metal composite hydroxide 10 represented by the general formula (3).
[0155] It should be noted that the composition of the shell of the lithium metal composite oxide (second particle) can be obtained, for example, by quantitative analysis of energy dispersive X-ray analysis (EDX) in cross-sectional observation using a scanning transmission electron microscope (STEM). In addition, the composition of the metal element other than lithium in the shell of the second particle can be adjusted to the above range by, for example, setting the composition of the shell of the metal composite hydroxide 10 used as a precursor to the range of the above general formula (2), and the composition of lithium in the shell of the second particle can be adjusted to the above range by setting the mixing ratio of the precursor and the lithium compound to the range described later.
[0156] (Structure of the shell)
[0157] In the second particle having the same particle size as the volume average particle size (MV) of the positive electrode active material (i.e., a particle size in the range of ±10% relative to the MV), the thickness of the shell portion in the direction from the particle surface to the center portion is 10% to 40% relative to the radius of the second particle, preferably 10% to 30%, and more preferably 10% to 20%. When the thickness of the shell portion is within the above range, the thermal stability and weather resistance of the secondary battery used as the positive electrode active material are excellent. It should be noted that the thickness and radius of the shell portion are the same as those of the above-mentioned metal composite hydroxide 10, and are values measured by observing the cross section of the lithium metal composite oxide using a scanning transmission electron microscope (STEM) or the like.
[0158] The thickness of the shell portion in the direction from the surface of the second particle to the center portion can be, for example, 0.2 μm or more and 1.6 μm or less, preferably 0.5 μm or more and 1.5 μm or less, and more preferably 0.6 μm or more and 1.0 μm or less. When the lower limit of the thickness of the shell portion is the above range, a positive electrode active material having excellent thermal stability and weather resistance can be obtained. In addition, when the upper limit of the thickness of the shell portion is the above range, the volume of the core portion having a high nickel ratio can be increased, and the secondary battery obtained using the positive electrode active material has a high battery capacity.
[0159] [Specific surface area of positive electrode active material]
[0160] The specific surface area of the positive electrode active material is preferably 0.1 m 2 / g above 3m 2 / g or less, more preferably 0.5m 2 / g above 2.5m 2 / g or less, more preferably 0.9m 2 / g above 2m 2 When the specific surface area is within the above range, the contact area between the positive electrode active material and the electrolyte in the positive electrode of the secondary battery is large, which can improve the output characteristics of the secondary battery. On the other hand, the specific surface area of the positive electrode active material is less than 0.1 m 2 / g, the reaction area between the positive electrode active material and the electrolyte in the positive electrode of the secondary battery cannot be fully ensured, and it is sometimes difficult to improve the output characteristics. In addition, when the specific surface area is too large, the reactivity of the positive electrode active material and the electrolyte in the positive electrode of the secondary battery becomes too high, so the thermal stability is sometimes reduced. It should be noted that the specific surface area of the positive electrode active material can be measured, for example, by the BET method using nitrogen adsorption.
[0161] [Tap density of positive electrode active material]
[0162] In recent years, in order to extend the use time of portable electronic devices and the driving distance of electric vehicles, the high capacity of secondary batteries has become an important issue. In addition, the electrode thickness of the secondary battery is sometimes required to be set to a few microns due to the packaging of the entire battery and the problem of electronic conductivity. Therefore, in order to increase the capacity of the secondary battery and reduce the electrode thickness, it is not only important to increase the capacity per unit mass of the positive electrode active material, but also to improve the filling property of the positive electrode active material and realize the high capacity per unit volume of the secondary battery. Here, the tap density becomes an indicator of the filling property of the positive electrode active material in the positive electrode.
[0163] The tap density of the positive electrode active material is preferably 2.0 g / cm 3 More preferably, 2.2 g / cm 3 More preferably, 2.3 g / cm 3 The tap density of the positive electrode active material is less than 2.0 g / cm 3 When the filling property is low, the battery capacity of the secondary battery as a whole cannot be fully improved. On the other hand, the upper limit of the tap density is not particularly limited, for example, 3.0 g / cm 3 The tap density refers to the bulk density of a sample powder collected in a container after being tapped 100 times in accordance with JIS Z-2504, and can be measured using a vibration specific gravity meter.
[0164] It should be noted that there is no particular limitation on the method for producing the positive electrode active material as long as the above-mentioned metal composite hydroxide can be used as a precursor to synthesize the positive electrode active material having the above-mentioned predetermined structure, average particle size and particle size distribution. When using the method for producing the positive electrode active material for a non-aqueous electrolyte secondary battery of the present embodiment described later, the positive electrode active material can be easily obtained on an industrial scale.
[0165] [Battery characteristics of positive electrode active materials]
[0166] It should be noted that, when the positive electrode active material according to this embodiment is used to form, for example Figure 5When the 2032-type button-type battery CBA is measured by the method described in the embodiment, the initial charge capacity can be set to, for example, 180 mAh / g or more, preferably 190 mAh / g or more, and more preferably 200 mAh / g or more. In addition, the initial discharge capacity can be set to, for example, 180 mAh / g or more, preferably 190 mAh / g or more.
[0167] In addition, although the positive electrode active material involved in the present embodiment has a high ratio of nickel, the oxygen release amount measured by the method described in the embodiments described later can be set to, for example, 12% by mass or less, preferably 10% by mass or less, and more preferably 8% by mass or less. It should be noted that the lower limit of the oxygen release amount is not particularly limited, for example, 1% by mass or more. In addition, the positive electrode active material involved in the present embodiment can be set to, for example, 0.3% by mass or less, preferably 0.2% by mass or less, and more preferably 0.15% by mass, after 24 hours of exposure, as measured by the method described in the embodiments described later. It should be noted that the moisture content after 24 hours of exposure is not particularly limited, for example, 0.01% by mass or more.
[0168] 4. Method for producing positive electrode active material for non-aqueous electrolyte secondary battery
[0169] Figure 3 1 is a diagram showing an example of a method for producing a positive electrode active material for a non-aqueous electrolyte secondary battery according to the present embodiment (hereinafter also referred to as a "method for producing a positive electrode active material"). Figure 3 As shown, the method for manufacturing the positive electrode active material comprises: a mixing step (step S30) of mixing the above-mentioned metal composite hydroxide and a lithium compound to form a lithium mixture; and a calcining step (step S40) of calcining the lithium mixture at a temperature of 650 to 900° C. in an oxidizing atmosphere.
[0170] The manufacturing method of this embodiment can easily manufacture the positive electrode active material on an industrial scale. Figure 4 The heat treatment step (step S20) and the pre-sintering step are shown in the figure. It should be noted that in this specification, the "metal composite hydroxide" mixed with the lithium compound without heat treatment and the "metal composite hydroxide and / or metal composite oxide" mixed with the lithium compound after the heat treatment step (step S20) are also collectively referred to as "precursor". The following is a description of each step.
[0171] (1) Mixing process (step S30)
[0172] like Figure 3 , 4As shown, the mixing process (step S30) is a process of mixing a metal composite hydroxide or at least one of a metal composite hydroxide and a metal composite oxide obtained by heat-treating the metal composite hydroxide with a lithium compound to obtain a lithium mixture. It should be noted that in the mixing process (step S30), a compound containing element M and a precursor may also be mixed with the lithium compound.
[0173] The mixing ratio of the precursor and the lithium compound can be adjusted so that the ratio (Li / Me) of the sum of the metal atoms other than lithium in the lithium mixture (Me) to the number of lithium atoms (Li) is greater than 0.95 and less than 1.5, preferably greater than 1.0 and less than 1.2, and more preferably greater than 1.0 and less than 1.1. It should be noted that the sum of the metal atoms other than lithium (Me) specifically refers to the sum of the number of atoms of nickel, cobalt, manganese and element M. That is, since Li / Me does not change before and after the sintering process (step S40), it is necessary to mix the precursor and the lithium compound so that the Li / Me in the mixing process (step S30) becomes the Li / Me of the target positive electrode active material.
[0174] The lithium compound used in the mixing step (step S30) is not particularly limited. In view of the ease of obtaining, lithium hydroxide, lithium nitrate, lithium carbonate or a mixture thereof is preferably used. In particular, in view of the ease of operation and the stability of quality, lithium hydroxide or lithium carbonate is preferably used.
[0175] In addition, the precursor and the lithium compound are preferably fully mixed to the extent that no fine powder is produced. When the mixing is insufficient, Li / Me will have deviations between the particles of the obtained positive electrode active material, and sometimes sufficient battery characteristics cannot be obtained. It should be noted that a common mixer can be used in the mixing. As a mixer, for example, an oscillating mixer, a Lodige mixer, a Julia mixer, a V-type mixer, etc. can be used.
[0176] [Heat treatment process (step S20)]
[0177] In addition, in the method for producing the positive electrode active material of the present embodiment, a heat treatment step (step S20, see step S30) for heat treating the metal composite hydroxide may be arbitrarily provided before the mixing step (step S30). Figure 4 ). The heat treatment step (step S20) is a step of heating the metal composite hydroxide to remove at least a portion of the remaining water contained in the metal composite hydroxide. When the heat treatment is included before the mixing step (step S30), the remaining water until the calcination step (step S40) can be reduced to a certain amount, and the composition deviation of the obtained positive electrode active material can be reduced.
[0178] Through the heat treatment process (step S20), at least one of a metal composite hydroxide and a metal composite oxide obtained by heat-treating the above-mentioned metal composite hydroxide can be obtained. That is, the obtained particles include a metal composite hydroxide from which at least a portion of the remaining water is removed, a metal composite oxide obtained by converting the metal composite hydroxide into an oxide, or a mixture thereof.
[0179] The temperature of the heat treatment can be set to, for example, 105°C to 750°C, or 105°C to 200°C. When the temperature of the heat treatment is less than 105°C, the remaining water in the metal composite hydroxide cannot be fully removed, and sometimes the deviation cannot be fully suppressed. On the other hand, when the heating temperature exceeds 700°C, not only can a better effect not be expected, but the production cost will also increase.
[0180] It should be noted that in the heat treatment process (step S20), as long as the water is removed to the extent that the ratio of the number of atoms of the metal components other than lithium and lithium in the positive electrode active material does not deviate, it is not necessary to convert all the metal composite hydroxides into metal composite oxides. In addition, from the viewpoint of making the ratio of the number of atoms of the metal components other than lithium and lithium in the positive electrode active material less deviating, it is preferably heated to above 400°C to convert all the metal composite hydroxides into metal composite oxides. It should be noted that by analyzing the metal components contained in the metal composite hydroxide / metal composite oxide after heat treatment in advance and determining the mixing ratio with the lithium compound, the above deviation can be further suppressed.
[0181] The atmosphere for heat treatment is not particularly limited, as long as it is non-reducing atmosphere, preferably carried out in the air flow that can be simply carried out. In addition, the heat treatment time is not particularly limited, from the viewpoint of fully removing the remaining moisture in the metal composite hydroxide, preferably set as more than 1 hour, more preferably set as more than 5 hours and less than 15 hours.
[0182] [Firing process (step S40)]
[0183] like Figure 3 , Figure 4 As shown, the calcination step (step S40) is a step of calcining the lithium mixture at a temperature of 650°C to 900°C to diffuse lithium in the precursor to obtain a lithium metal composite oxide.
[0184] In the firing process (step S40), the gradient of the composition of the core-shell structure inside the particles forming the precursor will be homogenized due to the diffusion of elements caused by heat. The higher the temperature during firing or the longer the firing time, the more significant the homogenization of the composition becomes. Therefore, if suitable firing conditions are not selected, the lithium metal composite oxide obtained after firing is sometimes unable to maintain the core-shell structure in the precursor and make the secondary particles have a uniform composition as a whole. Therefore, by appropriately adjusting the firing conditions within a specific range, a lithium metal composite oxide having the above-mentioned core-shell structure can be obtained. Below, an example of a preferred range of firing conditions is described.
[0185] (Firing temperature)
[0186] The calcination temperature of the lithium mixture is 650°C to 900°C, preferably 650°C to 850°C. When the calcination temperature is less than 650°C, lithium cannot be fully diffused inside the particles of the precursor, and the remaining lithium and unreacted precursor will remain, resulting in insufficient crystallinity of the obtained lithium metal composite oxide. On the other hand, when the calcination temperature exceeds 950°C, the particles of the lithium metal composite oxide are sintered violently, causing abnormal grain growth, and the proportion of amorphous coarse particles sometimes increases.
[0187] (Firing time)
[0188] In the sintering time, the holding time at the above-mentioned sintering temperature is preferably more than 2 hours, more preferably more than 4 hours and less than 10 hours. When the holding time at the sintering temperature is less than 2 hours, lithium cannot be fully diffused inside the particles of the precursor, and the remaining lithium and unreacted precursor will remain, resulting in concerns that the crystallinity of the obtained lithium metal composite oxide becomes insufficient. On the other hand, when it exceeds 10 hours, the diffusion of transition metal elements (Ni, Co, Mn, etc.) proceeds, and the core-shell structure is lost, and the target battery characteristics are sometimes not obtained. It should be noted that the sintering time can be appropriately adjusted within the range of the above-mentioned sintering temperature to obtain a second particle with a core-shell structure.
[0189] The heating rate in the calcining process (step S40) is preferably 2°C / min to 10°C / min, more preferably 3°C / min to 10°C / min. Furthermore, in the calcining process, the temperature is preferably maintained at a temperature near the melting point of the lithium compound for 1 hour to 5 hours, more preferably 2 hours to 5 hours. Thus, the precursor and the lithium compound can react more uniformly.
[0190] In addition, after the holding time is over, the cooling rate from the sintering temperature to at least 200°C is preferably 2°C / minute or more and 10°C / minute or less, more preferably 3°C / minute or more and 7°C / minute or less. By controlling the cooling rate to the above range, the productivity of the positive electrode active material can be ensured, and the equipment such as the sagger can be suppressed from being damaged due to rapid cooling.
[0191] (Firing atmosphere)
[0192] The atmosphere during sintering is preferably an oxidizing atmosphere, more preferably an atmosphere with an oxygen concentration of 18 volume % or more and 100 volume % or less, and particularly preferably a mixed atmosphere of oxygen and an inert gas at the above oxygen concentration. That is, sintering is preferably carried out in the atmosphere or an oxygen flow. When the oxygen concentration is less than 18 volume %, there is a concern that the crystallinity of the lithium metal composite oxide becomes insufficient.
[0193] It should be noted that the furnace used in the sintering process (step S40) is not particularly limited, as long as the lithium mixture can be heated in the atmosphere or oxygen flow. Among them, from the viewpoint of keeping the atmosphere in the furnace uniform, an electric furnace that does not produce gas is preferably used, and any of intermittent or continuous electric furnaces can be used appropriately. In this regard, the furnace used in the heat treatment process and the pre-sintering process described later is also the same.
[0194] [Pre-firing process]
[0195] In addition, when lithium hydroxide or lithium carbonate is used as the lithium compound, a pre-calcination step of pre-calcining the lithium mixture may be performed after the mixing step (step S30) and before the calcination step (step S40). In the pre-calcination, for example, heat treatment may be performed at a temperature lower than the calcination temperature in the calcination step (step S40) and at a temperature of 350°C to 800°C, preferably 450°C to 780°C. When the pre-calcination step is performed, lithium can be fully diffused in the precursor, and more uniform lithium metal composite oxide particles can be obtained.
[0196] It should be noted that, in the pre-sintering process, the holding time at the above temperature is preferably 1 hour or more and 10 hours or less, preferably 3 hours or more and 6 hours or less. In addition, the atmosphere in the pre-sintering process is the same as the sintering process described later, preferably an oxidizing atmosphere, more preferably an atmosphere with an oxygen concentration of 18 volume % or more and 100 volume % or less.
[0197] [Crushing process]
[0198] In addition, the lithium metal composite oxide obtained by the calcining process (step S40) can be directly used as a positive electrode active material. In addition, when agglomeration or mild sintering occurs in the lithium metal composite oxide in the calcining process (step S40), it can also be used as a positive electrode active material after the process (crushing process) of crushing the lithium metal composite oxide is performed. When the crushing process is performed, the average particle size and particle size distribution of the obtained lithium metal composite oxide can be adjusted to a suitable range. It should be noted that crushing refers to the operation of applying mechanical energy to the agglomerate formed by multiple secondary particles generated by sintering necking between secondary particles during calcining, so that the secondary particles themselves are separated almost without destruction, and the agglomerate is disassembled. As a method of crushing, a known method can be used, for example, a pin mill, a hammer mill, etc. can be used. It should be noted that at this time, it is preferred to adjust the crushing force to a suitable range so as not to destroy the secondary particles.
[0199] 5. Non-aqueous electrolyte secondary battery
[0200] The non-aqueous electrolyte secondary battery (hereinafter also referred to as "secondary battery") involved in this embodiment has a positive electrode, a negative electrode and a non-aqueous electrolyte, and the positive electrode contains the above-mentioned positive electrode active material. It should be noted that the secondary battery involved in this embodiment can have, for example, a positive electrode, a negative electrode, a separator and a non-aqueous electrolyte, and can also have a positive electrode, a negative electrode and a solid electrolyte. In addition, any secondary battery is a secondary battery that is charged and discharged by the separation and insertion of lithium ions, for example, it can be a non-aqueous electrolyte secondary battery or an all-solid lithium secondary battery. In addition, the secondary battery can be composed of the same components as the known lithium-ion secondary battery.
[0201] Hereinafter, as an example of a secondary battery involved in this embodiment, each constituent material of a secondary battery using a non-aqueous electrolyte and a method for manufacturing the same are described. It should be noted that the embodiments described below are merely illustrative, and the method for manufacturing a secondary battery can be implemented based on the embodiments described in this specification and in various modified and improved ways based on the knowledge of those skilled in the art. In addition, the use of the secondary battery obtained by the manufacturing method involved in this embodiment is not particularly limited.
[0202] (positive electrode)
[0203] The positive electrode contains the positive electrode active material. The positive electrode can be manufactured, for example, as shown below. It should be noted that the method for manufacturing the positive electrode is not limited to the following method, and other methods can also be used.
[0204] First, the positive electrode active material, the conductive material and the binder are mixed, and then activated carbon, a solvent for viscosity adjustment and the like are added as needed, and the mixture is kneaded to prepare a positive electrode mixture paste. It should be noted that the constituent materials of the positive electrode mixture paste are not particularly limited, and materials equivalent to known positive electrode mixture pastes can be used.
[0205] The mixing ratio of each material in the positive electrode mixture paste is not particularly limited and is appropriately adjusted according to the performance of the required secondary battery. The mixing ratio of the material can be set to the same range as the positive electrode mixture paste of the known secondary battery. For example, when the total mass of the solid component of the positive electrode mixture excluding the solvent is set to 100 parts by mass, the content of the positive electrode active material can be set to 60 parts by mass or less and 95 parts by mass or less, the content of the conductive material can be set to 1 part by mass or less and 20 parts by mass or less, and the content of the binder can be set to 1 part by mass or less and 20 parts by mass or less.
[0206] As the conductive agent, for example, graphite (natural graphite, artificial graphite, expanded graphite, etc.), carbon black materials such as acetylene black and Ketjen black, etc. can be used.
[0207] The binder (adhesive) is a substance that plays a role in binding the active material particles, and examples thereof include polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), fluororubber, ethylene propylene diene rubber, styrene butadiene, cellulose resin, polyacrylic acid, and the like.
[0208] It should be noted that, as needed, the positive electrode active material, the conductive material and the activated carbon can also be dispersed, and the solvent for dissolving the binder (binder) is added to the positive electrode mixture paste. As a solvent, an organic solvent such as N-methyl-2-pyrrolidone (NMP) can be used. In addition, in the positive electrode mixture, activated carbon can be added to increase the double layer capacity.
[0209] Next, the obtained positive electrode mixture paste is applied to the surface of a collector such as aluminum foil, dried, and the solvent is dispersed to produce a sheet-shaped positive electrode. If necessary, in order to increase the electrode density, pressure can also be applied by roller pressing, etc. The sheet-shaped positive electrode can be cut into appropriate sizes according to the target battery, and then provided for the production of the battery.
[0210] (negative electrode)
[0211] The negative electrode can use metallic lithium, lithium alloy, etc. In addition, the negative electrode can also be formed as follows: a binder is mixed in a negative electrode active material capable of absorbing and releasing lithium ions, and a suitable solvent is added to make a paste to obtain a negative electrode mixture, and the negative electrode mixture is applied to the surface of a metal foil collector such as copper, dried, and compressed as needed to increase the electrode density, thereby forming.
[0212] As the negative electrode active material, for example, a powder of a carbon material such as a sintered organic compound such as natural graphite, artificial graphite, phenolic resin, or coke can be used. As the negative electrode binder, similar to the positive electrode, a fluorine-containing resin such as PVDF can be used. In addition, as a solvent for dispersing these active materials and the binder, an organic solvent such as N-methyl-2-pyrrolidone can be used.
[0213] (Diaphragm)
[0214] The separator is placed between the positive electrode and the negative electrode. The separator is a material that separates the positive electrode and the negative electrode and holds the electrolyte. A thin film such as polyethylene or polypropylene having many micropores can be used.
[0215] (Non-aqueous electrolyte)
[0216] The non-aqueous electrolyte is formed by dissolving the lithium salt as a supporting electrolyte in an organic solvent. As an organic solvent, a kind selected from cyclic carbonates such as ethylene carbonate, propylene carbonate, butylene carbonate, trifluoropropylene carbonate, and chain carbonates such as diethyl carbonate, dimethyl carbonate, methyl ethyl carbonate, dipropyl carbonate, and then ether compounds such as tetrahydrofuran, 2-methyltetrahydrofuran, dimethoxyethane, methyl ethyl sulfone, butane sultone, phosphorus compounds such as triethyl phosphate, trioctyl phosphate, etc. can be used alone, or mixed with more than two kinds of use.
[0217] As supporting electrolytes, LiPF6, LiBF4, LiClO4, LiAsF6, LiN(CF3SO2)2, and their composite salts can be used. Furthermore, the non-aqueous electrolyte may also contain a radical scavenger, a surfactant, a flame retardant, and the like.
[0218] [Solid Electrolyte]
[0219] As the non-aqueous electrolyte, a solid electrolyte can be used. A solid electrolyte has the property of being able to withstand high voltage. Examples of the solid electrolyte include inorganic solid electrolytes and organic solid electrolytes.
[0220] Examples of the inorganic solid electrolyte include oxide-based solid electrolytes and sulfide-based solid electrolytes.
[0221] The oxide-based solid electrolyte is not particularly limited, and for example, a substance containing oxygen (O) and having lithium ion conductivity and electronic insulation can be suitably used. As the oxide-based solid electrolyte, for example, lithium phosphate (Li3PO4), Li3PO4N X 、LiBO2N X, LiNbO3, LiTaO3, Li2SiO3, Li4SiO4-Li3PO4, Li4SiO4-Li3VO4, Li2O-B2O3-P2O5, Li2O-SiO2, Li2O-B2O3-ZnO, Li 1+X Al X Ti 2-X (PO4)3(0≤X≤1), Li 1+X Al X Ge 2-X (PO4)3(0≤X≤1), LiTi2(PO4)3, Li 3X La 2 / 3-X TiO3(0≤X≤2 / 3), Li5La3Ta2O 12 、Li7La3Zr2O 12 、Li6BaLa2Ta2O 12 , Li 3.6 Si 0.6 P 0.4 One or more selected from O4, etc.
[0222] As the sulfide-based solid electrolyte, there is no particular limitation, and for example, a substance containing sulfur (S) and having lithium ion conductivity and electronic insulation can be suitably used. As the sulfide-based solid electrolyte, for example, one or more selected from Li2S-P2S5, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li2S-B2S3, Li3PO4-Li2S-Si2S, Li3PO4-Li2S-SiS2, LiPO4-Li2S-SiS, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, etc. can be used.
[0223] It should be noted that as the inorganic solid electrolyte, substances other than those listed above may be used, for example, Li3N, LiI, Li3N-LiI-LiOH, etc. may be used.
[0224] The organic solid electrolyte is not particularly limited as long as it is a polymer compound showing ion conductivity, and for example, polyethylene oxide, polypropylene oxide, copolymers thereof, etc. can be used. In addition, the organic solid electrolyte may contain a supporting electrolyte (lithium salt).
[0225] It should be noted that a solid electrolyte can also be used to form a secondary battery instead of a non-aqueous electrolyte. The solid electrolyte will not decompose even at a high potential, so there will be no gas generation and thermal runaway caused by the decomposition of the electrolyte during charging as seen in the non-aqueous electrolyte, so it has high thermal stability. Therefore, when used in a lithium ion secondary battery using the positive electrode active material of the present invention, a secondary battery with higher thermal stability can be obtained.
[0226] (Battery shape and structure)
[0227] The shape of the nonaqueous electrolyte secondary battery of the present embodiment composed of the positive electrode, negative electrode and nonaqueous electrolyte described above can be various shapes such as cylindrical type and stacked type. In the case of any shape, the positive electrode and the negative electrode are stacked across the separator to form an electrode body, the obtained electrode body is impregnated with a nonaqueous electrolyte, and the positive electrode collector and the positive terminal connected to the outside and the negative electrode collector and the negative terminal connected to the outside are connected using a collector lead, and the nonaqueous electrolyte secondary battery is completed by sealing in a battery box.
[0228] It should be noted that the secondary battery involved in this embodiment is not limited to the form of using a non-aqueous electrolyte as a non-aqueous electrolyte, for example, it can also be made into a secondary battery using a solid non-aqueous electrolyte, that is, an all-solid battery. When making an all-solid battery, the composition other than the positive electrode active material can be changed as needed. It should be noted that when a solid electrolyte is used, the solid electrolyte can also serve as a diaphragm.
[0229] (Characteristics of non-aqueous electrolyte secondary batteries)
[0230] Since the nonaqueous electrolyte secondary battery of this embodiment uses the above-mentioned positive electrode active material as the positive electrode material, the battery capacity, thermal stability and weather resistance are excellent. It can be said that the battery capacity, thermal stability and weather resistance are more excellent than those of the conventional secondary battery using the positive electrode active material containing the lithium nickel composite oxide.
[0231] (use)
[0232] As mentioned above, the battery capacity, thermal stability and weather resistance of the nonaqueous electrolyte secondary battery of the present embodiment are excellent, and can be suitably used for the power supply of the small portable electronic device (notebook type personal computer, mobile phone etc.) requiring these characteristics at a high level. In addition, the thermal stability of the nonaqueous electrolyte secondary battery of the present invention is also excellent, and not only can miniaturization and high output be realized, but also expensive protection circuit can be simplified, so it can also be suitably used for the power supply of the transportation equipment with limited space.
[0233] Example
[0234] Hereinafter, the metal composite hydroxide and the method for producing the positive electrode active material of the present invention will be described using examples, but the present invention is not limited to these examples.
[0235] It should be noted that, in the following examples and comparative examples, unless otherwise specified, each sample of the special grade reagent manufactured by Wako Pure Chemical Industries, Ltd. was used in the preparation of the composite hydroxide particles and the positive electrode active material. In addition, in the whole process of the nucleation step and the particle growth step, the pH value of the reaction aqueous solution was measured by a pH controller (made by Nissin Rika, NPH-690D), and the supply of the sodium hydroxide aqueous solution was adjusted based on the measured value, so that the pH value of the reaction aqueous solution in each step was controlled to be within the range of ±0.2.
[0236] [Example 1]
[0237] 1. Production of metal composite hydroxides
[0238] [Preparation of First and Second Raw Aqueous Solutions]
[0239] As the first raw material aqueous solution, nickel sulfate, cobalt sulfate, and manganese sulfate were dissolved in water so that the molar ratio of each metal element was Ni:Co:Mn=88:9:3, and a 2 mol / L aqueous solution was prepared. In addition, as the second raw material aqueous solution, nickel sulfate, cobalt sulfate, and manganese sulfate were dissolved in water so that the molar ratio of each metal element was Ni:Co:Mn=45:10:45, and a 2 mol / L aqueous solution was prepared.
[0240] [First crystallization step]
[0241] First, 14 L of water was added to a 60 L reaction tank, and the temperature in the tank was set to 40° C. while stirring. At this time, nitrogen was circulated in the reaction tank for 30 minutes to make the reaction atmosphere a non-oxidizing atmosphere with an oxygen concentration of 2% by volume or less. Next, 25% by mass sodium hydroxide aqueous solution and 25% by mass ammonia water were appropriately supplied to the reaction tank, and the pH value was adjusted to 12.5 based on a liquid temperature of 25° C. and the ammonium ion concentration was 10 g / L, thereby forming a pre-reaction aqueous solution.
[0242] Next, the first raw material aqueous solution, 25 mass % sodium hydroxide aqueous solution and 25 mass % ammonia water are added to the reaction tank at the same time, the pH value is maintained at 12.5 based on the liquid temperature of 25°C, the ammonium ion concentration is 10 g / L, and the reaction temperature is 40°C, and the metal composite hydroxide is formed by a continuous crystallization method of continuous coprecipitation. After the reaction tank is stabilized, a slurry (reaction aqueous solution) containing the metal composite hydroxide (mainly the core of the first particle) is recovered from the overflow. The product in the reaction aqueous solution is 90 to 110 g / L.
[0243] [Second Crystallization Step]
[0244] For the slurry (reaction aqueous solution) containing the core obtained by the first crystallization, a predetermined amount is transferred to a 60L reaction tank (intermittent crystallization device) different from the reaction tank used for the first crystallization, sulfuric acid is added, and the pH value is adjusted to 11.6 based on a liquid temperature of 25°C, thereby forming a reaction aqueous solution for shell crystallization. After confirming that the pH value reaches a predetermined value (11.6), a second raw material aqueous solution, a 25% by mass sodium hydroxide aqueous solution, and a 25% by mass ammonia solution are added to the reaction tank at the same time, so that the shell grows on the surface of the particles (mainly the core of the first particle) obtained by the first crystallization step. It should be noted that the reaction atmosphere, reaction temperature, and ammonium ion concentration in the second crystallization step are the same as those in the first crystallization step.
[0245] In the crystallization step, the supply amounts of the first and second raw aqueous solutions were adjusted so that the amount of metal elements supplied in each step relative to the total amount of metal elements supplied was (first crystallization step:second crystallization step) = 75 mol %:25 mol %.
[0246] 2. Evaluation of metal composite hydroxides
[0247] [composition]
[0248] By analysis using an ICP emission spectrophotometer (manufactured by Shimadzu Corporation, ICPE-9000), it was confirmed that the obtained metal composite hydroxide was composed of the general formula: Ni 0.773 Co 0.092 Mn 0.135 (OH)2 represents.
[0249] [Average particle size and particle size distribution]
[0250] The average particle size of the metal composite hydroxide was measured using a laser diffraction scattering particle size analyzer (Microtrac HRA, manufactured by Nikkiso Co., Ltd.), and D10 and D90 were measured to calculate [(D90-D10) / MV] as an index representing the width of the particle size distribution.
[0251] [Particle structure]
[0252] A portion of the metal composite hydroxide was embedded in a resin and processed by focused ion beam to a state where the cross section could be observed. The cross section was then observed by STEM-EDX (manufactured by Hitachi High-Technologies Corporation, HD-2300A) (see Figure 6). The results confirmed that: among the observable metal composite hydroxides, the metal composite hydroxides whose cross-sectional particle diameter is in the range of the volume average particle diameter (MV) (±10%) contain secondary particles formed by the aggregation of multiple primary particles, and have a core-shell structure, wherein the core-shell structure is composed of a core portion and a shell portion, wherein the core portion has a radius of 84% of the thickness relative to the radius of the secondary particle in the direction from the surface of the particle to the center, and the shell portion has a thickness of 16% relative to the radius of the secondary particle.
[0253] 3. Manufacturing of positive electrode active material
[0254] The obtained metal composite hydroxide (precursor) was heat-treated at 120°C for 12 hours in an air flow (oxygen concentration: 21 volume %) (heat treatment step). The heat-treated precursor was fully mixed with lithium hydroxide so that Li / Me was 1.01 to obtain a lithium mixture (mixing step). During the mixing, an oscillating mixer device (TURBULA Type T2C manufactured by WAB) was used.
[0255] The obtained lithium mixture is heated to 800°C at a heating rate of 3°C / min in an oxygen (oxygen concentration: 100% by volume) gas flow, and is kept at this temperature for 6 hours to be sintered, and then cooled to room temperature at a cooling rate of about 4°C / min to obtain a positive electrode active material (sintering process). The obtained positive electrode active material is agglomerated or slightly sintered. Therefore, the positive electrode active material is crushed to adjust the average particle size and particle size distribution (crushing process).
[0256] [composition]
[0257] The analysis using ICP emission spectrophotometer confirmed that the positive electrode active material is composed of the general formula: Li 1.01 Ni 0.77 Co 0.09 Mn 0.14 O2 means.
[0258] [Particle structure]
[0259] A portion of the positive electrode active material was embedded in the resin, and after the cross section was observed by focused ion beam processing, it was observed by STEM-EDX (HD-2300A manufactured by Hitachi High-Technologies Corporation). The results confirmed that among the positive electrode active materials that can be observed, the positive electrode active material with a cross-sectional particle size in the range of volume average particle size (MV) (±10%) contained a plurality of secondary particles formed by agglomeration of primary particles, and had a core-shell structure, which consisted of a core and a shell, and the core had a radius of 87% thickness relative to the radius of the secondary particle in the direction from the surface of the particle to the center, and the shell had a thickness of 13%.
[0260] [Average particle size and particle size distribution]
[0261] The average particle size of the positive electrode active material was measured using a laser diffraction scattering particle size analyzer (Microtrac HRA, manufactured by Nikkiso Co., Ltd.), and D10 and D90 were measured to calculate [(D90-D10) / MV] as an index representing the width of the particle size distribution. The results are shown in Table 2.
[0262] [Specific surface area and tap density]
[0263] The specific surface area was measured using a flow gas adsorption specific surface area measuring device (Multisorb, manufactured by Yuasa Ionics Co., Ltd.), and the tap density was measured using a tap compactor (KRS-406, manufactured by Kurachi Scientific Instruments Co., Ltd.).
[0264] [Weather resistance]
[0265] 10 g of the positive electrode active material was stored in a constant temperature and humidity chamber (IW242 manufactured by Yamato Scientific Co., Ltd.) at 25°C x RH 50% for 24 hours, and the moisture content was evaluated by Karl Fischer titration. The moisture content after storage for 24 hours was 0.08%.
[0266] 4. Fabrication of secondary batteries
[0267] 52.5 mg of the positive electrode active material obtained as described above, 15 mg of acetylene black and 7.5 mg of PTFE were mixed, compression-molded into a shape of 11 mm in diameter and 100 μm in thickness at a pressure of 100 MPa, and then dried in a vacuum dryer at 120° C. for 12 hours to prepare a positive electrode PE.
[0268] Next, the positive electrode PE was used to make a 2032-type button-type battery CBA in a glove box with an Ar atmosphere whose dew point was managed to -80°C. The negative electrode NE of the 2032-type button-type battery CBA uses lithium metal with a diameter of 17 mm and a thickness of 1 mm, and the electrolyte uses an equal mixture of 1M ethylene carbonate (EC) and diethyl carbonate (DEC) with LiClO4 as the supporting electrolyte (manufactured by Toyama Pharmaceutical Industry Co., Ltd.). In addition, the separator SE uses a polyethylene porous membrane with a film thickness of 25 μm. It should be noted that the 2032-type button-type battery CBA has a gasket GA, and is assembled into a button-shaped battery using a positive electrode tank PC and a negative electrode tank NC.
[0269] 5. Battery evaluation
[0270] [Initial charge and discharge capacity]
[0271] After making a 2032-type button-type battery CBA, place it for about 24 hours. After the open circuit voltage OCV (Open Circuit Voltage) stabilizes, set the current density relative to the positive electrode to 0.1 mA / cm 2 , charged to a cut-off voltage of 4.3V, the capacity at this time is taken as the initial charge capacity, and after resting for 1 hour, discharged to a cut-off voltage of 3.0V, the discharge capacity at this time is measured, and the charge and discharge test is performed to obtain the initial charge and discharge capacity. The results are shown in Table 2. It should be noted that the determination of the initial discharge capacity is performed using a multi-channel voltage / current generator (manufactured by Advantex Co., Ltd., R6741A).
[0272] [Thermal stability]
[0273] The thermal stability evaluation of the positive electrode is carried out by quantifying the amount of oxygen released by bringing the positive electrode active material to an overcharged state and heating it. The above-mentioned 2032-type button-type battery is made and CCCV charging (constant current-constant voltage charging) is performed at a rate of 0.2C until the cut-off voltage is 4.5V. Then, the button-type battery is disassembled, and only the positive electrode is carefully taken out to prevent short circuit, and it is washed with DMC (dimethyl carbonate) and dried. About 2 mg of the dried positive electrode is measured and heated from room temperature to 450°C at a heating rate of 10°C / min using a gas chromatograph mass spectrometer (GCMS, Shimadzu Corporation, QP-2010plus). Helium is used as a carrier gas. The generation behavior of oxygen (m / z=32) generated during heating is measured, and the amount of oxygen generated is semi-quantitatively measured based on the height and peak area of the maximum oxygen generation peak obtained, and they are used as evaluation indicators of thermal stability. The semi-quantitative value of the oxygen generation amount was calculated by extrapolating a calibration curve obtained from the measurement results of injecting pure oxygen gas as a standard sample into GCMS. As a result, an oxygen release amount of 7.6 wt% was confirmed.
[0274] (Example 2)
[0275] In the crystallization step, the supply amount of the first and second raw material aqueous solutions was adjusted so that the amount of the metal element supplied in each step relative to the total amount of the metal element supplied was the first crystallization step: the second crystallization step = 65 mol %: 35 mol %, except that the same operation as Example 1 was performed to obtain a metal composite hydroxide, a positive electrode active material and a secondary battery, which were evaluated. The results are shown in Tables 1 and 2.
[0276] (Example 3)
[0277] In the crystallization step, the supply amount of the first and second raw material aqueous solutions was adjusted so that the amount of the metal element supplied in each step relative to the total amount of the metal element supplied was the first crystallization step: the second crystallization step = 85 mol %: 15 mol %, except that the same operation as Example 1 was performed to obtain a metal composite hydroxide, a positive electrode active material and a secondary battery, which were evaluated. The results are shown in Tables 1 and 2.
[0278] (Example 4)
[0279] In the first crystallization step (nucleus formation), the atomic ratio (molar ratio) of the metal elements contained in the first raw material aqueous solution was adjusted to Ni:Co:Mn=94:3:3, and the same operation as in Example 1 was performed to obtain a metal composite hydroxide, a positive electrode active material and a secondary battery, which were evaluated. The results are shown in Tables 1 and 2.
[0280] [Example 5]
[0281] In the first crystallization step (nucleus formation), the atomic ratio (molar ratio) of the metal elements contained in the first raw material aqueous solution was adjusted to Ni:Co:Mn=70:15:15, and the same operation as in Example 1 was performed to obtain a metal composite hydroxide, a positive electrode active material and a secondary battery, which were evaluated. The results are shown in Tables 1 and 2.
[0282] [Example 6]
[0283] In the second crystallization step (shell formation), the atomic ratio (molar ratio) of the metal elements contained in the second raw material aqueous solution was adjusted to Ni:Co:Mn=55:25:20, and the same operation as in Example 1 was performed to obtain a metal composite hydroxide, a positive electrode active material and a secondary battery, which were evaluated. The results are shown in Tables 1 and 2.
[0284] [Example 7]
[0285] A positive electrode active material and a secondary battery were obtained and evaluated in the same manner as in Example 1 except that the same metal composite hydroxide as in Example 1 was used and the calcination temperature was changed to 900° C. The results are shown in Table 2.
[0286] [Example 8]
[0287] A positive electrode active material and a secondary battery were obtained and evaluated in the same manner as in Example 1 except that the same metal composite hydroxide as in Example 1 was used and the calcination temperature was set to 650° C. The results are shown in Table 2.
[0288] [Comparative Example 1]
[0289] In the crystallization step, the supply amount of the first and second raw material aqueous solutions was adjusted so that the amount of the metal element supplied in each step relative to the total amount of the metal element supplied was the first crystallization step: the second crystallization step = 60 mol %: 40 mol %, except that the same operation as Example 1 was performed to obtain a metal composite hydroxide, a positive electrode active material and a secondary battery, which were evaluated. The results are shown in Tables 1 and 2.
[0290] [Comparative Example 2]
[0291] In the crystallization step, the supply amount of the first and second raw material aqueous solutions was adjusted so that the amount of the metal element supplied in each step relative to the total amount of the metal element supplied was the first crystallization step: the second crystallization step = 90 mol %: 10 mol %, except that the same operation as Example 1 was performed to obtain a metal composite hydroxide, a positive electrode active material and a secondary battery, which were evaluated. The results are shown in Tables 1 and 2.
[0292] [Comparative Example 3]
[0293] In the first crystallization step (nucleus formation), the atomic ratio (molar ratio) of the metal elements contained in the first raw material aqueous solution was adjusted to Ni:Co:Mn=97:2:1, and the same operation as in Example 1 was performed to obtain a metal composite hydroxide, a positive electrode active material and a secondary battery, which were evaluated. The results are shown in Tables 1 and 2.
[0294] [Comparative Example 4]
[0295] In the first crystallization step (nucleus formation), the atomic ratio (molar ratio) of the metal elements contained in the first raw material aqueous solution was adjusted to Ni:Co:Mn=38:31:31, and the atomic ratio (molar ratio) of the metal elements contained in the second raw material aqueous solution was adjusted to Ni:Co:Mn=40:20:40. The same operation as in Example 1 was performed to obtain a metal composite hydroxide, a positive electrode active material and a secondary battery, and the results are shown in Tables 1 and 2.
[0296] [Comparative Example 5]
[0297] In the second crystallization step (shell formation), the atomic ratio (molar ratio) of the metal elements contained in the second raw material aqueous solution was adjusted to a ratio of Ni:Co:Mn=60:10:30, and the same operation as in Example 1 was performed to obtain a metal composite hydroxide, a positive electrode active material and a secondary battery, which were evaluated. The results are shown in Tables 1 and 2.
[0298] [Comparative Example 6]
[0299] The same metal composite hydroxide as in Example 1 was used, and the calcination temperature was set to 920° C. in the calcination step. The same operation as in Example 1 was performed to obtain a metal composite hydroxide, a positive electrode active material, and a secondary battery, and these were evaluated. The results are shown in Tables 2 and 3. Figure 3 .
[0300] [Comparative Example 7]
[0301] A positive electrode active material and a secondary battery were obtained and evaluated in the same manner as in Example 1 except that the same metal composite hydroxide as in Example 1 was used and the calcination temperature was set to 630° C. in the calcination step.
[0302] [Comparative Example 8]
[0303] In the crystallization step, the atomic ratio (molar ratio) of the metal elements contained in each raw material aqueous solution was Ni:Co:Mn=77:9:14, and the first and second crystallization steps were carried out using raw material aqueous solutions having the same atomic ratio of metal elements. The same operation as in Example 1 was performed to obtain a metal composite hydroxide, a positive electrode active material and a secondary battery, and the results are shown in Tables 1 and 2.
[0304] [Table 1]
[0305]
[0306] [Table 2]
[0307]
[0308] (Evaluation results)
[0309] In the positive electrode active material using the metal composite hydroxide obtained in the embodiment as a precursor, the moisture content after 24 hours of exposure, which is an indicator of weather resistance, is small, and in the evaluation battery, the initial charge and discharge capacity is high, and the oxygen release amount, which is an indicator of thermal stability, is small. This shows that in the positive electrode active material using the metal composite hydroxide obtained in the embodiment as a precursor, it is possible to take into account the high charge and discharge capacity, thermal stability and weather resistance of the secondary battery at a high level.
[0310] On the other hand, in the metal composite hydroxide and the positive electrode active material obtained in Comparative Example 1, the thickness of the shell portion with a low nickel ratio was more than 40%, respectively, and the initial charge and discharge capacity was reduced compared with Example 5 (overall nickel ratio: 64 mol%) in which the nickel ratio (relative to the molar ratio of all metals other than lithium) in the overall composition was lower. In addition, in the metal composite hydroxide and the positive electrode active material obtained in Comparative Example 2, the thickness of the shell portion with a low nickel ratio was less than 10%, respectively, and the thermal stability and weather resistance were insufficient.
[0311] In addition, in the metal composite hydroxide and the positive electrode active material obtained in Comparative Example 3, the nickel ratio of the core portion was 97 mol%, and the thermal stability and weather resistance were insufficient. In addition, in the metal composite hydroxide and the positive electrode active material obtained in Comparative Example 4, the nickel ratio of the core portion was less than 40 mol%, and a high initial charge and discharge capacity was not obtained.
[0312] In addition, in the metal composite hydroxide and the positive electrode active material obtained in Comparative Example 5, since the nickel ratio in the shell is 60 mol %, the thermal stability and weather resistance are insufficient, and the initial charge and discharge capacity is also reduced compared with Example 1 (overall nickel ratio: 77 mol %) in which the nickel ratio in the overall composition is lower.
[0313] In addition, the calcination temperature of the positive electrode active material obtained in Comparative Example 6 exceeds 900°C, and the thermal stability and weather resistance are insufficient compared with the positive electrode active material of Example 1 using the same metal composite hydroxide as a precursor. In addition, the calcination temperature of the positive electrode active material obtained in Comparative Example 7 is less than 650°C, and the initial charge and discharge capacity is reduced compared with the positive electrode active material of Example 1 using the same metal composite hydroxide as a precursor.
[0314] In addition, although the positive electrode active material obtained in Comparative Example 8 has the same overall composition as the positive electrode active material of Example 1, it does not have a core-shell structure and has a uniform composition inside the particles. Therefore, compared with the positive electrode active material of Example 1, its thermal stability and weather resistance are low, and its initial charge and discharge capacity is also low.
[0315] It should be noted that the technical scope of the present invention is not limited to the methods described in the above-mentioned embodiments, etc. One or more elements described in the above-mentioned embodiments, etc. may be omitted. In addition, the elements described in the above-mentioned embodiments, etc. may be appropriately combined. In addition, within the scope permitted by law, the contents of Special Application No. 2018-029555, which is a Japanese patent application, and all the documents cited in this specification are cited as part of the description herein.
[0316] Explanation of symbols
[0317] 10…Metal composite hydroxide
[0318] 11…The First Particle
[0319] 11a…Core
[0320] 11b…shell
[0321] C…Center
[0322] t…shell thickness
[0323] R11 ...the radius of the first particle
[0324] R 11a ...radius of the core
[0325] CBA…Button battery
[0326] PC…Positive electrode tank
[0327] NC…Cathode tank
[0328] GA...Gasket
[0329] PE…positive electrode
[0330] NE…Negative electrode
[0331] SE…diaphragm.
Claims
1. A metal composite hydroxide, which is a general formula (1): Ni 1-x-y Co x Mn y M z (OH) 2+α A metal composite hydroxide represented by 0.02≤x≤0.3, 0.02≤y≤0.3, 0≤z≤0.05, -0.5≤α≤0.5, 0.6≤1-xy≤0.95 are satisfied, M is at least one element selected from Mg, Ca, Al, Si, Fe, Cr, V, Mo, W, Nb, Ti and Zr, In the particle size distribution obtained by the laser diffraction scattering method, [(D90-D10) / MV] indicating the particle size dispersion index calculated from D90 and D10 and the volume average particle size MV is 0.80 or more, The metal composite hydroxide includes a first particle having a core portion formed inside the particle and a shell portion formed around the core portion. The core part is produced by a continuous crystallization device in which a product precipitated by a crystallization method is recovered in an overflow manner, and the particle size dispersion index [(D90-D10) / MV] is 0.80 or more, The shell is formed on the surface of the core using an intermittent crystallization device. The composition of the core is represented by the general formula (2): Ni 1-x1-y1 Co x1 Mn y1 M z1 (OH) 2+α1 Indicates that, 0.7≤(1-x1-y1)≤0.96, 0≤z1≤0.05, -0.5≤α1≤0.5, The composition of the shell is given by the general formula (3): Ni 1-x2-y2 Co x2 Mn y2 M z2 (OH) 2+α2 Indicates that, (1-x1-y1) / (1-x2-y2)>1.0, 0<(1-x2-y2)<0.6, 0≤z2≤0.05, -0.5≤α2≤0.5, 0.05<x2≤0.3, In the first particles having a particle size within a range of ±10% relative to the volume average particle size MV, the shell portion has a thickness from the surface of the particle toward the center that is 10% to 20% relative to the radius of the first particle.
2. The metal composite hydroxide according to claim 1, wherein The composition of the shell is given by the general formula (3): Ni 1-x2- y2 Co x2 Mn y2 M z2 (OH) 2+α2 Indicates that, among them, (1-x1-y1) / (1-x2-y2)>1.0, 0.45≤(1-x2-y2)≤0.55, 0≤z2≤0.05, -0.5≤α2≤0.5, 0.05<x2<0.
3.
3. The metal composite hydroxide according to claim 1 or claim 2, wherein The volume average particle size MV is 7 μm or more and 20 μm or less.
4. The metal composite hydroxide according to claim 1 or claim 2, wherein The element M is uniformly present inside and / or on the surface of the first particle.
5. A method for producing the metal composite hydroxide according to claim 1, The manufacturing method comprises the following steps: A first crystallization step, supplying a first raw material aqueous solution containing nickel and at least one of cobalt, manganese and the element M, and adjusting the reaction aqueous solution to a pH value of more than 12.0 and less than 13.5 based on a liquid temperature of 25° C. to perform crystallization, continuously performing nucleation and particle growth to form the core portion; and In a second crystallization step, a second raw material aqueous solution containing a smaller amount of nickel than the first raw material aqueous solution is supplied to a reaction aqueous solution containing the core portion and adjusted to a pH value of 10.5 to 12.0 based on a liquid temperature of 25° C., thereby forming the shell portion around the core portion. The first crystallization step is performed by a continuous crystallization method in which a precipitated product is recovered by an overflow method, and the second crystallization step is performed by a batch crystallization method.
6. A positive electrode active material for a non-aqueous electrolyte secondary battery, comprising a compound of the general formula (4): Li 1+a Ni 1-x- y Co x Mn y M z O 2+β A positive electrode active material for a non-aqueous electrolyte secondary battery of a lithium metal composite oxide, wherein -0.05≤a≤0.50, 0.02≤x≤0.3, 0.02≤y≤0.3, 0≤z≤0.05, -0.5≤β≤0.5, 0.6≤1-xy≤0.95, M is at least one element selected from Mg, Ca, Al, Si, Fe, Cr, V, Mo, W, Nb, Ti and Zr, In the particle size distribution obtained by the laser diffraction scattering method, [(D90-D10) / MV] indicating the particle size dispersion index calculated from D90 and D10 and the volume average particle size MV is 0.80 or more, The lithium metal composite oxide includes a second particle having a core portion formed inside the particle and a shell portion formed around the core portion. In the second particle, the core portion is composed of the general formula (5): Li 1+a1 Ni 1-x1-y1 Co x1 Mn y1 M z1 O 2+β1 Indicates that, -0.05≤a1≤0.50, 0.7≤(1-x1-y1)≤0.96, 0≤z1≤0.05, -0.5≤β1≤0.5, The composition of the shell is represented by the general formula (6): Li 1+a2 Ni 1-x2-y2 Co x2 Mn y2 M z2 O 2+β2 Indicates that, -0.05≤a2≤0.50, (1-x1-y1) / (1-x2-y2)>1.0, 0<(1-x2-y2)<0.6, 0≤z2≤0.05, -0.5≤β2≤0.5, 0.05<x2<0.3, In the second particles having a particle size within a range of ±10% relative to the volume average particle size MV, the shell portion has a thickness of 10% to 20% relative to the radius of the second particle in a direction from the surface of the second particle toward the center.
7. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 6, wherein The composition of the shell is represented by the general formula (6): Li 1+a2 Ni 1-x2-y2 Co x2 Mn y2 M z2 O 2+β2 It means that -0.05≤a2≤0.50, (1-x1-y1) / (1-x2-y2)>1.0, 0.45<(1-x2-y2)≤0.55, 0≤z2≤0.05, -0.5≤β2≤0.5, 0.05<x2<0.
3.
8. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 6 or claim 7, wherein In the particle size distribution obtained by laser diffraction scattering method, the volume average particle size MV is 5 μm or more and 20 μm or less, and the tap density is 2.0 g / cm 3 above.
9. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 6 or claim 7, wherein The element M is uniformly distributed inside the lithium metal composite oxide and / or covers at least a portion of the surface of the lithium metal composite oxide.
10. A method for producing a positive electrode active material for a non-aqueous electrolyte secondary battery, comprising: a mixing step of mixing the metal composite hydroxide according to any one of claims 1 to 4 with a lithium compound to obtain a lithium mixture; and In the calcining step, the lithium mixture is calcined at a temperature of 650° C. to 900° C. in an oxidizing atmosphere.
11. A method for producing a positive electrode active material for a non-aqueous electrolyte secondary battery, comprising: A heat treatment step of heat-treating the metal composite hydroxide according to any one of claims 1 to 4; a mixing step of mixing at least one of the metal composite hydroxide and the metal composite oxide obtained after the heat treatment with a lithium compound to obtain a lithium mixture; and In the calcining step, the lithium mixture is calcined at a temperature of 650° C. to 900° C. in an oxidizing atmosphere. 12 . A non-aqueous electrolyte secondary battery comprising: a positive electrode using the positive electrode active material according to claim 6 , a negative electrode, and a non-aqueous electrolyte.
Citation Information
Patent Citations
Nickel manganese composite hydroxide particle and production method thereof, positive electrode active material for nonaqueous electrolyte secondary battery and production method thereof, and nonaqueous electrolyte secondary battery
JP2012256435A
Compound oxide, complex transition metal compound, production method of compound oxide, cathode active material for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery
JP2014040363A
Combine
JP2018029555A
Gradient cathode material for lithium rechargeable batteries
WO2002103824A2